Organic thin film and method for producing organic thin film, organic electroluminescence element, display device, lighting device, organic thin film solar cell, thin film transistor, photoelectric conversion element, coating composition, and material for organic electroluminescence element
By using organic materials with polyindole ring structure as electron injection layer in organic electroluminescent devices, the problem of insufficient electron injection and transport performance in the prior art is solved, and more efficient electron injection and longer equipment life are achieved.
Patent Information
- Application Number
- JP2023194392
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-03
- Filing Date
- 2023-11-15
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2040-09-04
AI Technical Summary
Existing organic electroluminescent (EL) devices have shortcomings in electron injection and delivery performance, especially the performance of the electron injection layer is not ideal.
Organic materials containing polyindole ring structure are used as materials for the electron injection layer. These materials have nitrogen atoms with high electron donation performance, which can improve electron injection capacity through multivariate coordination and form negative charges through hydrogen bonds with other organic materials, further improving electron injection and transport performance.
It significantly improves the electronic injection and delivery performance of organic EL equipment, extends the service life of the equipment, and simplifies the structure of the equipment.
Smart Images

Figure 0007657893000033 
Figure 0007657893000034 
Figure 0007657893000035
Abstract
Description
[Technical field]
[0001] The present invention relates to an organic thin film and a method for producing an organic thin film, an organic electroluminescence (hereinafter, electroluminescence (field emission) may be abbreviated as "EL") element, a display device, a lighting device, an organic thin film solar cell, a thin film transistor, a photoelectric conversion element, a coating composition, and a material for an organic electroluminescence element. [Background technology]
[0002] Organic EL elements are thin, soft, and flexible. Furthermore, displays using organic EL elements are capable of displaying images with higher brightness and resolution than the currently mainstream liquid crystal display devices and plasma display devices. Furthermore, displays using organic EL elements have a wider viewing angle than liquid crystal display devices. For this reason, it is expected that displays using organic EL elements will be used more widely in the future as displays for televisions, mobile phones, and the like. Organic EL elements are also expected to be used as lighting devices.
[0003] An organic EL element is a laminate of a cathode, a light-emitting layer, and an anode. In an organic EL element, the difference in energy between the work function of the anode and the highest occupied molecular orbital (HOMO) of the light-emitting layer is smaller than the difference in energy between the work function of the cathode and the lowest unoccupied molecular orbital (LUMO) of the light-emitting layer. Therefore, it is more difficult to inject electrons from the cathode into the light-emitting layer than to inject holes from the anode. For this reason, in conventional organic EL elements, an electron injection layer is disposed between the cathode and the light-emitting layer to promote the injection of electrons from the cathode into the light-emitting layer. In addition, efforts have been made to improve electron injection and transport properties by doping a layer disposed between the cathode and the light-emitting layer with a dopant (see, for example, Non-Patent Document 1 and Non-Patent Document 2).
[0004] An example of the electron injection layer of an organic EL element is an inorganic oxide layer (see, for example, Non-Patent Document 3). However, the electron injection property of an inorganic oxide layer is insufficient. There is also a technique for improving the electron injection of an organic EL element by forming an electron injection layer on an inorganic oxide layer. For example, Non-Patent Document 4 describes an organic EL element having an electron injection layer made of polyethyleneimine. Non-Patent Document 5 describes that amines are effective in improving the electron injection rate. Non-Patent Documents 6, 7, 8, and 12 describe the effect of amino groups on electron injection at the interface between an electrode and an organic layer. Non-Patent Documents 10-11 report that phenanthroline derivatives promote electron emission from metal atoms due to their high coordination ability with metal ions, and greatly lower the electron injection barrier at the electrode-organic layer interface, and it is widely practiced to form an organic thin film consisting of only phenanthroline derivatives at the interface between an electrode and an organic layer. Furthermore, Patent Document 1 discloses an organic EL element in which a phenanthroline compound is used as an electron transporting host material, and the host material is doped with an inactive metal to lower the energy level of the LUMO of the electron transporting material, promoting electron injection, and lowering the driving voltage of the element. In addition, organic EL devices have been disclosed that use, as materials for the electron injection layer, compounds having a structure in which an amino group is bonded directly or via another group to a group derived from an electron transporting compound, or organic materials having an acid dissociation constant pKa of 1 or more (see Patent Documents 2 to 4). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2017 / 211100 [Patent Document 2] JP 2017-157743 A [Patent Document 3] JP 2019-176093 A [Patent Document 4] JP 2019-179863 A [Non-patent literature]
[0006] [Non-Patent Document 1] Karsten Walzer et al., Chemical Review, Vol. 107, 2007, p1233-1271 [Non-Patent Document 2] Peng Wei and 3 others, Journal of the American Chemical Society, Vol. 132, 2010, p. 8852 [Non-Patent Document 3] Jiangshan Chen et al., Journal of Materials Chemistry, Vol. 22, 2012, pp. 5164-5170 [Non-Patent Document 4] Hyosung Choi et al., Advanced Materials, Vol. 23, 2011, p. 2759 [Non-Patent Document 5] Yinhua Zho and 21 others, Science, Vol. 336, 2012, p. 327 [Non-Patent Document 6] Young-Hoon Kim and 5 others, "Advanced Functional Materials", 2014, DOI:10.1002 / adfm.201304163 [Non-Patent Document 7] Stephen Forfl and 4 others, "Advanced Materials", 2014, DOI:10.1002 / adma.201304666 [Non-Patent Document 8] Stephen Forfl and 5 others, "Advanced Materials", Vol. 26, 2014, DOI:10.1002 / adma.201400332 [Non-Patent Document 9] Peng Wei and 3 others, Journal of the American Chemical Society, Vol. 132, 2010, p. 8852 [Non-Patent Document 10] Hiroyuki Yoshida, Journal of Physical Chemistry (J. Phys. Chem. C20151194324459-24464), Vol. 119, 2015, p. 24459 [Non-Patent Document 11] Zhengyang Bin and 7 others, Nature Communications, Vol. 10, 2019, p. 866 [Non-Patent Document 12] Hirohiko Fukagawa and 5 others, "Advanced Materials", Vol. 31, 2019, p1904201 Summary of the Invention [Problem to be solved by the invention]
[0007] However, in conventional organic EL devices including an electron injection layer, there has been a demand for further improvements in the electron injection and electron transport properties.
[0008] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an organic thin film that can provide excellent electron injection and electron transport properties when used in an electron injection layer of an organic EL device, a coating composition that can be suitably used in producing the organic thin film, and a material for organic EL devices that serves as a raw material for the organic thin film and coating composition. Another object of the present invention is to provide an organic EL element using the organic thin film of the present invention, a display device and a lighting device including this organic EL element, and an organic thin film solar cell, a photoelectric conversion element, and an organic thin film transistor including the organic thin film of the present invention. [Means for solving the problem]
[0009] The present inventors have focused on organic materials capable of multidentate coordination that have an electron-donating nitrogen atom in a heterocycle as a material for the electron injection layer of an organic EL device, and have found that an organic thin film containing a compound with a specific structure that has multiple pyridine rings in its skeleton and a material that transports electrons can be used as the electron injection layer of an organic EL device.
[0010] That is, due to the high electron donating property of the nitrogen atom contained in the compound represented by the general formula (1) of the present invention, in addition to the effect of improving the electron injection property due to the coordination interaction with the inorganic material, when another organic material (a material that transports electrons) is adjacent to the compound, the nitrogen atom can form a hydrogen bond with the organic material and impart a small amount of charge, which generates a negative charge on the other organic material side, and this is also presumably a factor in improving the electron injection property.
[0011] The present invention has been completed based on the above findings, and the gist of the present invention is as follows. [1] An organic thin film, characterized in that it is a single film containing a first material, which is a compound having a structure represented by the following general formula (1), and a second material that transports electrons, or a laminated film of a film containing the first material and a film containing the second material.
[0012] [ka] (In general formula (1), X 1 , X 2 are the same or different and each represents a nitrogen atom, an oxygen atom, a sulfur atom, or a divalent linking group which may have a substituent. L represents a direct bond or a p-valent linking group. n represents a number of 0 or 1, and p represents a number of 1 to 4. q represents a number of 0 or 1, and when p is 1, q is 0. R 1 ~R 3 m may be the same or different and represents a monovalent substituent. 1 ~m 3 are the same or different and represent a number from 0 to 3.)
[0013] [2] The organic thin film according to [1], wherein the first material is a compound in which n is 0 in the general formula (1).
[0014] [3] A laminated film comprising an oxide layer and a layer of the organic thin film according to [1] or [2] formed on the oxide layer.
[0015] [4] An organic electroluminescence element having an emitting layer between a cathode and an anode, the organic electroluminescence element comprising the organic thin film according to [1] or [2] or the laminated film according to [3] between the cathode and the emitting layer.
[0016] [5] The organic electroluminescence element according to [4], further comprising an inorganic oxide layer between the cathode and the organic thin film.
[0017] [6] The organic electroluminescent element according to [4] or [5], further comprising a laminated film including a film containing the first material and the second material and a film containing the second material between the cathode and the light-emitting layer.
[0018] [7] The organic electroluminescence element according to [6], further comprising a layer containing the second material between the light-emitting layer and the film containing the first material and the second material.
[0019] [8] The organic electroluminescent element according to [6], further comprising a layer containing the second material between the cathode and the film containing the first material and the second material.
[0020] [9] The organic electroluminescence element according to any one of [4] to [8], further comprising a layer containing the second material between the anode and the light-emitting layer.
[0021]
[10] The organic electroluminescence device according to any one of [4] to [9], wherein the light-emitting layer contains the second material.
[0022]
[11] A material for an organic electroluminescence device, comprising a phenanthroline compound having a structure represented by the following general formula (2):
[0023] [ka] (In general formula (2), R 4 , R 5 m may be the same or different and represents a dialkylamino group or an alkoxy group. 4 , m 5 are the same or different and represent the number 1 or 2.)
[0024]
[12] An organic electroluminescence element having an emitting layer between a cathode and an anode, characterized in that the organic electroluminescence element has a layer between the cathode and the anode containing the material for organic electroluminescence elements according to
[11] .
[0025]
[13] The organic electroluminescence device according to
[12] , further comprising a layer containing the material for an organic electroluminescence device according to
[11] between the cathode and the light-emitting layer.
[0026]
[14] The organic electroluminescence device according to
[12] or
[13] , further comprising an inorganic oxide layer between the cathode and the layer containing the material for an organic electroluminescence device according to
[11] .
[0027]
[15] A display device comprising the organic electroluminescence element according to any one of [4] to
[10] and
[12] to
[14] .
[16] A lighting device comprising the organic electroluminescence element according to any one of [4] to
[10] and
[12] to
[14] .
[0028]
[17] A material for an organic thin-film solar cell, comprising a phenanthroline compound having a structure represented by the following general formula (2):
[0029] [ka] (In general formula (2), R 4 , R 5 are the same or different and each represents a dialkylamino group or an alkoxy group. 4 , m 5 are the same or different and represent the number 1 or 2.)
[0030]
[18] An organic thin-film solar cell comprising either the organic thin-film according to [1] or [2], the laminated film according to [3], or a layer containing the material for organic thin-film solar cells according to
[17] .
[0031]
[19] A material for a photoelectric conversion element, comprising a phenanthroline compound having a structure represented by the following general formula (2):
[0032] [ka] (In general formula (2), R 4 , R 5 are the same or different and each represents a dialkylamino group or an alkoxy group. 4 , m 5 are the same or different and represent the number 1 or 2.)
[0033]
[20] A photoelectric conversion element comprising any one of the organic thin film according to [1] or [2], the laminated film according to [3], or a layer containing the material for photoelectric conversion elements according to
[19] .
[0034]
[21] A material for a thin film transistor, comprising a phenanthroline compound having a structure represented by the following general formula (2):
[0035] [ka] (In general formula (2), R 4 , R 5 m may be the same or different and represents a dialkylamino group or an alkoxy group.4 , m 5 are the same or different and represent the number 1 or 2.)
[0036]
[22] A thin film transistor comprising any one of the organic thin film according to [1] or [2], the laminated film according to [3], or a layer containing the material for thin film transistors according to
[21] .
[0037]
[23] A coating composition comprising a first material, which is a compound having a structure represented by the following general formula (1), and a second material that transports electrons:
[0038] [ka] (In general formula (1), X 1 , X 2 are the same or different and each represents a nitrogen atom, an oxygen atom, a sulfur atom, or a divalent linking group which may have a substituent. L represents a direct bond or a p-valent linking group. n represents a number of 0 or 1, and p represents a number of 1 to 4. q represents a number of 0 or 1, and when p is 1, q is 0. R 1 ~R 3 m may be the same or different and represents a monovalent substituent. 1 ~m 3 are the same or different and represent a number from 0 to 3.)
[0039]
[24] A coating composition comprising a first material, which is a compound having a structure represented by the following general formula (1):
[0040] [ka] (In general formula (1), X 1 , X 2 are the same or different and each represents a nitrogen atom, an oxygen atom, a sulfur atom, or a divalent linking group which may have a substituent. L represents a direct bond or a p-valent linking group. n represents a number of 0 or 1, and p represents a number of 1 to 4. q represents a number of 0 or 1, and when p is 1, q is 0. R 1 ~R 3m may be the same or different and represents a monovalent substituent. 1 ~m 3 are the same or different and represent a number from 0 to 3.)
[0041]
[25] A method for producing an organic thin film, comprising the steps of: forming, on a surface to be formed, a single film containing a first material, which is a compound having a structure represented by the following general formula (1), and a second material that transports electrons; or forming, in order, a film containing the first material and a film containing the second material on a surface to be formed:
[0042] [ka] (In general formula (1), X 1 , X 2 are the same or different and each represents a nitrogen atom, an oxygen atom, a sulfur atom, or a divalent linking group which may have a substituent. L represents a direct bond or a p-valent linking group. n represents a number of 0 or 1, and p represents a number of 1 to 4. q represents a number of 0 or 1, and when p is 1, q is 0. R 1 ~R 3 m may be the same or different and represents a monovalent substituent. 1 ~m 3 are the same or different and represent a number from 0 to 3.)
[0043]
[26] A method for producing an organic thin film, comprising the step of forming a film containing a first material, which is a compound having a structure represented by the following general formula (1), on a surface to be formed:
[0044] [ka] (In general formula (1), X 1 , X 2 are the same or different and each represents a nitrogen atom, an oxygen atom, a sulfur atom, or a divalent linking group which may have a substituent. L represents a direct bond or a p-valent linking group. n represents a number of 0 or 1, and p represents a number of 1 to 4. q represents a number of 0 or 1, and when p is 1, q is 0. R 1 ~R 3m may be the same or different and represents a monovalent substituent. 1 ~m 3 are the same or different and represent a number from 0 to 3.)
[0045]
[27] The method for producing an organic thin film according to
[26] , wherein the surface to be formed contains a second material. Effect of the Invention
[0046] The organic thin film of the present invention includes a first material made of a specific electron-donating organic material and a second material that transports electrons. Therefore, when the organic thin film of the present invention is used in, for example, the electron injection layer of an organic EL device, excellent electron injection and transport properties are obtained, and further, an effect of extending the life of the organic EL device is obtained. Since the organic EL element of the present invention has the organic thin film of the present invention between the cathode and the light-emitting layer, the organic thin film provides excellent electron injection and electron transport properties, and further provides the effect of extending the life of the organic EL element. In addition, the organic thin film of the present invention, which includes a first material made of a compound having a specific structure containing multiple pyridine rings in its skeleton, which is a polydentate organic material containing an electron-donating nitrogen atom in a heterocycle, and a second material transporting electrons, can be formed by either coating or vapor deposition, so there are fewer process restrictions when manufacturing an organic EL device including the organic thin film of the present invention, and it is easy to use as a material for a layer constituting an organic EL device. The method for manufacturing an organic thin film of the present invention is a method for manufacturing such an organic thin film of the present invention.
[0047] The coating composition of the present invention includes a first material made of a specific organic material capable of multidentate coordination containing an electron-donating nitrogen atom in a heterocycle, and a second material that transports electrons. Therefore, by applying the coating composition of the present invention to a surface on which an organic thin film is to be formed, an organic thin film suitable for an electron injection layer of an organic EL device can be obtained.
[0048] The material for organic EL devices of the present invention is a useful material used in the organic thin film or coating composition of the present invention used in the production of organic EL devices, etc. In addition, the material is also useful in that it can be used alone as an electron injection layer or electron transport layer.
[0049] The display device and lighting device of the present invention have a low driving voltage and excellent characteristics since they include the organic EL element of the present invention. Moreover, the organic thin-film solar cell, photoelectric conversion element and organic thin-film transistor of the present invention have excellent properties since they contain the organic thin film of the present invention. [Brief description of the drawings]
[0050] [Figure 1] FIG. 1 is a diagram showing electrostatic potentials of phenanthroline derivatives calculated using quantum chemical calculations. [Diagram 2] This figure shows the most stable structure, the highest occupied molecular orbital, and the ionization energy of a two-molecule system of a phenanthroline derivative and triphenylamine, calculated using quantum chemical calculations. [Diagram 3] FIG. 1 is a comparison of 1H-NMR measurement results for a boron compound alone and for a boron compound coexisting with phenanthroline. [Figure 4] FIG. 1 is a schematic cross-sectional view illustrating an example of an organic EL element of the present invention. [Diagram 5] FIG. 1 is a schematic cross-sectional view illustrating an example of an organic EL element of the present invention. [Figure 6] FIG. 2 is a schematic cross-sectional view showing another example of the laminate structure of the organic EL element of the present invention. [Figure 7] FIG. 2 is a schematic cross-sectional view showing another example of the laminate structure of the organic EL element of the present invention. [Figure 8-1] FIG. 1 is a schematic cross-sectional view showing an example of an organic thin film of the present invention. [Figure 8-2] FIG. 1 is a schematic cross-sectional view showing an example of an organic thin film of the present invention. [Figure 9-1] FIG. 1 is a schematic cross-sectional view showing an example of a laminate structure of an organic thin film of the present invention. [Figure 9-2] FIG. 1 is a schematic cross-sectional view showing an example of a laminate structure of an organic thin film of the present invention. [Figure 10-1] FIG. 1 is a schematic cross-sectional view showing an example of a laminate structure of an organic thin film of the present invention. [Figure 10-2] FIG. 1 is a schematic cross-sectional view showing an example of a laminate structure of an organic thin film of the present invention. [Figure 11-1] FIG. 1 is a schematic cross-sectional view showing an example of a laminate structure of an organic thin film of the present invention. [Figure 11-2] FIG. 1 is a schematic cross-sectional view showing an example of a laminate structure of an organic thin film of the present invention. [Figure 12-1] FIG. 1 is a schematic cross-sectional view showing an example of a laminate structure of an organic thin film of the present invention. [Figure 12-2] FIG. 1 is a schematic cross-sectional view showing an example of a laminate structure of an organic thin film of the present invention. [Figure 13-1] FIG. 1 is a schematic cross-sectional view showing an example of a laminate structure of an organic thin film of the present invention. [Figure 13-2] FIG. 1 is a schematic cross-sectional view showing an example of a laminate structure of an organic thin film of the present invention. [Figure 14-1] FIG. 1 is a schematic cross-sectional view showing an example of a laminate structure of an organic thin film of the present invention. [Figure 14-2] FIG. 1 is a schematic cross-sectional view showing an example of a laminate structure of an organic thin film of the present invention. [Figure 15] 1 is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements of Examples 1 and 2 and Comparative Example 1. [Figure 16] 1 is a graph showing the relationship between the applied voltage and the current density of the organic EL elements of Examples 1 and 2 and Comparative Example 1. [Figure 17] 1 is a graph showing the relationship between current density and external quantum efficiency of the organic EL elements of Examples 1 and 2 and Comparative Example 1. [Figure 18] 1 is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements of Examples 3 to 5 and Comparative Example 2. [Figure 19] 1 is a graph showing the relationship between the applied voltage and the current density of the organic EL elements of Examples 3 to 5 and Comparative Example 2. [Figure 20] 1 is a graph showing the relationship between current density and external quantum efficiency of the organic EL devices of Examples 3 to 5 and Comparative Example 2. [Figure 21] 1 is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements of Examples 6 and 7 and Comparative Example 2. [Figure 22] 1 is a graph showing the relationship between the applied voltage and the current density of the organic EL elements of Examples 6 and 7 and Comparative Example 2. [Figure 23] 1 is a graph showing the relationship between current density and external quantum efficiency of the organic EL elements of Examples 6 and 7 and Comparative Example 2. [Figure 24] 13 is a graph showing the relationship between the continuous driving time and the luminance of the organic EL elements of Examples 6 and 7. [Diagram 25] 1 is a graph showing the relationship between applied voltage and luminance of the organic EL elements of Examples 1 and 8. [Figure 26] 1 is a graph showing the relationship between the applied voltage and the current density of the organic EL elements of Examples 1 and 8. [Figure 27] 1 is a graph showing the relationship between current density and external quantum efficiency of the organic EL elements of Examples 1 and 8. [Figure 28] 1 is a graph showing the relationship between the continuous driving time and the luminance of the organic EL elements of Examples 1 and 8. [Figure 29] 1 is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements of Examples 9 to 13 and Comparative Example 3. [Diagram 30] FIG. 13 shows microscopic images of the light-emitting surfaces of the organic EL elements of Examples 12 and 13 and Comparative Example 3 when stored in the atmosphere without sealing. [Diagram 31] 1 is a graph showing the relationship between applied voltage and luminance of the organic EL elements of Example 14 and Comparative Example 4. [Diagram 32] 13 is a graph showing the relationship between the continuous driving time and the luminance of the organic EL elements of Example 14 and Comparative Example 4. [Diagram 33] 1 is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements of Example 15 and Comparative Example 5. [Diagram 34] 1 is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements of Example 16 and Comparative Example 6. [Diagram 35]1 is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements of Examples 17 to 20 and Comparative Example 7. [Diagram 36] 1 is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements of Example 21 and Comparative Example 8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0051] The present invention will be described in detail below. "Materials for organic thin films and organic EL devices" The organic thin film of the present invention comprises a first material, which is a compound having a structure represented by the following general formula (1), and a second material, which transports electrons and is different from the first material. The organic thin film of the present invention may be a single-layer film containing the first material and the second material, or a laminated film in which a layer containing the first material and a layer containing the second material are laminated.
[0052] [ka] (In general formula (1), X 1 , X 2 are the same or different and each represents a nitrogen atom, an oxygen atom, a sulfur atom, or a divalent linking group which may have a substituent. L represents a direct bond or a p-valent linking group. n represents a number of 0 or 1, and p represents a number of 1 to 4. q represents a number of 0 or 1, and when p is 1, q is 0. R 1 ~R 3 m may be the same or different and represents a monovalent substituent. 1 ~m 3 are the same or different and represent a number from 0 to 3.)
[0053] The first material constituting the organic thin film of the present invention is a material capable of multidentate coordination containing an electron-donating nitrogen atom in a heterocycle, and thus has the ability to stably form hydrogen bonds with the second material and generate a negative charge on the second material side. It is preferable that the first material has a large negative electrostatic potential at the nitrogen moiety, which is the electron-donating moiety. The larger the electrostatic potential of the first material, the higher the ability of the first material to generate a negative charge on the second material. Furthermore, it has been confirmed that the first material has the effect of improving the life of the element. Therefore, the organic thin film of the present invention can be used not only in elements composed of only organic compounds, but also in elements composed of organic and inorganic compounds, and can exhibit the effects of improving the electron injection properties and atmospheric stability, as well as extending the life of the elements. The organic thin film of the present invention is characterized in that it contains a compound having a structure represented by the above general formula (1) as a first material, and when the organic thin film of the present invention is used in an electron injection layer, excellent electron injection and electron transport properties are obtained. Such a compound having a structure represented by the above general formula (1) is a suitable compound as a material for an organic EL device. The phenanthroline compound represented by the above general formula (2) is included in the above general formula (1), and such a material for an organic EL device containing a phenanthroline compound represented by the above general formula (2) is also one aspect of the present invention. The "electrostatic potential" described in the present invention can be calculated using a quantum chemical calculation program such as GAUSSIAN. Although the absolute value of the calculated value varies depending on the basis functions used in the calculation, it is possible to discuss the correlation with the amount of negative charge generated using the relative values calculated using the same calculation method. As examples of the first material of the present invention, the electrostatic potential of the nitrogen site in the phenanthroline contained in each of the first materials was calculated under the following conditions. Functions used to calculate the most stable structures of phenanthroline compounds B3LYP / 6-31+G(d) Functions used in the calculation of electrostatic potentials of phenanthroline compounds B3LYP / 6-311++G(2df,2p)
[0054] The calculation results are shown in Figure 1. The calculated electrostatic potential of the part of phenanthroline, which is the most basic skeleton, where the coordinating nitrogen atom is close, surrounded by a dotted line, is shown. The electrostatic potential values of the other compounds 1 to 13 are the same as those of phenanthroline. As shown in Figure 1, the electrostatic potential value of phenanthroline is highly dependent on the substituents added. Large electrostatic potential values were obtained for compound 1, which was given an electron-donating substituent, a pyrrolidino group, compound 2, which was given a dimethylamine group, and compound 3, which was given a methoxy group. These compounds are particularly suitable as the first material because the electron-donating substituent increases the electron density of the phenanthroline skeleton, thereby improving the hydrogen bonding ability of the nitrogen atom and its coordination ability to inorganic compounds. In addition, for compounds represented by general formula (1) other than phenanthroline, when n is 1, the number of nitrogen atoms involved in hydrogen bonds and coordination with inorganic compounds is large, and therefore the electrostatic potential value is considered to be relatively large.
[0055] In addition to the compound having only one phenanthroline shown in FIG. 1, compounds having multiple phenanthrolines as shown in the following formulas (3-1) to (3-4) are also considered to be effective in generating negative charges and are suitable as the first material.
[0056] [ka]
[0057] The generation of negative charges caused by phenanthroline derivatives was also simulated using quantum chemical calculations. The results are shown in Figure 2. Various phenanthroline derivatives were used as the first material, and triphenylamine (TPA), which has a simple molecular structure, was used as the second material. The optimized structure of the two molecules was calculated, and the ionization energy of triphenylamine in the optimized structure was calculated.
[0058] As shown in Figure 2, in the optimized structure, a specific hydrogen atom of triphenylamine forms a hydrogen bond with the nitrogen atom of phenanthroline, and a change in the ionization energy is observed. Although there is no change in the distribution of the highest occupied molecular orbital in the two-molecule calculation, it can be seen that the ionization energy is smaller when a phenanthroline derivative with a larger electrostatic potential value is used. A smaller ionization energy means that it is easier to remove electrons from the triphenylamine molecule, which means that the triphenylamine is more likely to become negatively charged.The larger the electrostatic potential of the first material, the more negative charge can be generated in the second material. The presence of hydrogen bonds is shown in Figure 3. 1 This is suggested by H-NMR measurements. The measurements were performed using a simplified boron compound, and the proton peak position of the boron compound alone was compared with that of the boron compound in the presence of phenanthroline. The amount of phenanthroline added was 5 molar equivalents to the boron compound, and the measurement was performed in deuterated chloroform. Figure 3 shows that the peak position of the proton enclosed in the frame shifts to the high magnetic field side. This is because the electron density of the hydrogen atom of the boron compound increases due to the interaction between the boron compound and phenanthroline through hydrogen bonds.
[0059] X in the above general formula (1) 1 , X 2 are the same or different and represent a nitrogen atom, an oxygen atom, a sulfur atom or a divalent linking group which may have a substituent. Examples of the divalent linking group include divalent hydrocarbon groups and groups in which some of the carbon atoms of a hydrocarbon group have been substituted with a heteroatom such as a nitrogen atom, an oxygen atom or a sulfur atom. The hydrocarbon group preferably has 1 to 6 carbon atoms, and more preferably has 1, 2 or 6 carbon atoms. The hydrocarbon group may be linear, branched, cyclic, or a combination thereof. The divalent hydrocarbon group may be an alkylene group, which is a saturated hydrocarbon group, or an unsaturated hydrocarbon group such as an alkenylene group or an alkynylene group. Specifically, the divalent hydrocarbon group is preferably one represented by the following formulas (4-1) to (4-4). In the following formulas (4-1) to (4-4), R represents a substituent. X, including R in (4-1) to (4-4), 1 , X 2 Specific examples of the substituent in R 1 ~R 3 Examples of the monovalent substituent include the same groups as those of the monovalent substituent of the above.
[0060] [ka]
[0061] In the above general formula (1), L represents a direct bond or a p-valent linking group. Note that L becomes a direct bond only when p is 2. Examples of the p-valent linking group include a nitrogen atom, an oxygen atom, a sulfur atom, a carbon atom, and also a group obtained by removing p hydrogen atoms from a hydrocarbon group or a group in which some of the carbon atoms of a hydrocarbon group have been substituted with a hetero atom such as a nitrogen atom, an oxygen atom, or a sulfur atom. When the p-valent linking group has a carbon atom, it preferably has 1 to 30 carbon atoms, and more preferably has 1 to 20 carbon atoms. The hydrocarbon group may be linear, branched, cyclic, or a combination thereof. The hydrocarbon group may be any of a saturated hydrocarbon group, an unsaturated hydrocarbon group, and an aromatic hydrocarbon group. Examples of aromatic hydrocarbon groups include groups formed by removing a hydrogen atom from an aromatic compound such as a benzene ring, a naphthalene ring, an anthracene ring, a tetracene ring, a pentacene ring, a triphenylene ring, a pyrene ring, a fluorene ring, or an indene ring.
[0062] R in the above general formula (1) 1 ~R 3 are the same or different and represent monovalent substituents.Examples of the monovalent substituent include a fluorine atom; a haloalkyl group such as a fluoromethyl group, a difluoromethyl group, or a trifluoromethyl group; a linear or branched alkyl group having 1 to 20 carbon atoms such as a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, or a tert-butyl group; a cyclic alkyl group having 5 to 7 carbon atoms such as a cyclopentyl group, a cyclohexyl group, or a cycloheptyl group; a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, a butoxy group, an isobutoxy group, a tert-butoxy group, a pentyloxy group, a hexyloxy group, a heptyloxy group, or a methyloxy group. linear or branched alkoxy groups having 1 to 20 carbon atoms, such as a silyl group or an octyloxy group; a nitro group; a cyano group; an alkylamino group having an alkyl group having 1 to 10 carbon atoms, such as a methylamino group, an ethylamino group, a dimethylamino group or a diethylamino group; a cyclic amino group, such as a pyrrolidino group, a piperidino group or a morpholino group; a diarylamino group, such as a diphenylamino group or a carbazolyl group; an acyl group, such as an acetyl group, a propionyl group or a butyryl group; an alkenyl group having 2 to 30 carbon atoms, such as a styryl group; a halogen atom, such as a fluorine atom, an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a cyclic amino group having 1 to 10 carbon atoms, such as ... an aryl group having 5 to 20 carbon atoms which may be substituted with a silyl group, an amino group, or the like (specific examples of the aryl group are the same as those of the aromatic hydrocarbon group described above); a heterocyclic group containing one or more of a nitrogen atom, a sulfur atom, and an oxygen atom which may be substituted with a halogen atom such as a fluorine atom, an alkyl group having 1 to 20 carbon atoms, an alkoxy group, an amino group, or the like (the heterocyclic group may be one consisting of only one ring, or may be a compound in which a plurality of compounds consisting of only one aromatic heterocycle are directly bonded to each other at one carbon atom, or may be a condensed heterocyclic group. Specific examples of the heterocyclic group include Specific examples of aromatic heterocyclic groups include a thiophene ring, a furan ring, a pyrrole ring, a benzothiophene ring, a benzofuran ring, an indole ring, a dibenzothiophene ring, a dibenzofuran ring, a carbazole ring, a thiazole ring, a benzothiazole ring, an oxazole ring, a benzoxazole ring, an imidazole ring, a benzimidazole ring, a pyridine ring, a pyrimidine ring, a pyrazine ring, a pyridazine ring, a triazine ring, a quinoline ring, an isoquinoline ring, a quinoxaline ring, a benzothiadiazole ring, a phenanthridine ring, etc.); an ester group, a thioether group, etc.These groups may be substituted with a halogen atom, a hetero element, an alkyl group, an aromatic ring, or the like.
[0063] R in General (2) above 4 , R 5 are the same or different and represent a dialkylamino group or an alkoxy group. The dialkylamino group preferably has an alkyl group having 1 to 20 carbon atoms, such as a methyl group or an ethyl group. More preferably, the dialkylamino group has an alkyl group having 1 to 10 carbon atoms. The two alkyl groups in the dialkylamino group may have the same or different carbon numbers. Also preferred are amino groups in which two alkyl groups are linked, such as cyclic amino groups such as a piperidino group, a pyrrolidino group, or a morpholino group. The alkoxy group is R 1 ~R 3 is an alkoxy group.
[0064] In the above general formula (1), p represents a number from 1 to 4, and is preferably a number from 1 to 3. Specific examples of the compound in which p is 1 in general formula (1) include the compounds represented by the following formulas (5-1) to (5-9).
[0065] [ka]
[0066] In the above general formula (1), n represents the number 0 or 1, and in one preferred embodiment of the present invention, the compound represented by the above general formula (1) is a compound in which n is 0. Specific examples of the compound in which n is 0 in general formula (1) include the compounds represented by the above formulae (5-1) to (5-6).
[0067] The second material in the present invention may be any material capable of transporting electrons, and is preferably an organic material. More preferably, the second material is an organic material having a lowest unoccupied molecular orbital (LUMO) level of 2.0 eV to 4.0 eV, and among these, an n-type organic semiconductor material having a LUMO level of 2.5 eV to 3.5 eV. For example, any of the conventionally known materials shown below may be used as the material for the electron transport layer of an organic EL device, and among these, a material that satisfies the above LUMO level requirement is preferred. Specific examples of the second material include phosphine oxide derivatives such as phenyl-dipyrenylphosphine oxide (POPy2), pyridine derivatives such as tris-1,3,5-(3'-(pyridin-3''-yl)phenyl)benzene (TmPhPyB), 1,3,5-tris(6-(3-(pyridin-3-yl)phenyl)pyridin-2-yl)benzene, and 8,9-diphenyl-7,10-(3-(pyridin-3-yl))fluoranthene, quinoline derivatives such as (2-(3-(9-carbazolyl)phenyl)quinoline (mCQ), and 2-phenyl pyrimidine derivatives such as 2-methyl-4,6-bis(3,5-dipyridylphenyl)pyrimidine (BPyPPM) and 2-methyl-4,6-bis(3,5-dipyridylphenyl)pyrimidine, 9-(4-(4,6-diphenylpyrimidin-2-yl)phenyl)-9H-carbazole, pyrazine derivatives, phenanthroline derivatives such as bathophenanthroline (BPhen) and 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP), 2,4-bis(4-biphenyl)-6-(4'-(2-pyridinyl)-4-biphenyl)-[1,3, 5]triazine (MPT), tris-1,3,5-(3'-(pyridin-3''-yl)phenyl)triazine (TmPhPyTz), tris-1,3,5-([1,1'-biphenyl]-3-yl)triazine, 2-(3-(4,6-di(pyridin-3-yl)-1,3,5-triazin-2-yl)phenyl)-1-phenyl-1H-benzo[d]imidazole, 9-(4-(4,6-diphenyl-1,3,5-triazin-2-yl)phenyl)-9H-3,9'-bicarbazole, 9-(4-(4,6-diphenyl-1,3,5-triazin-2-yl)phenyl)-9H-3,9'-bicarbazole, triazine derivatives such as 11-(4,6-diphenyl-1,3,5-triazin-2-yl)-12-phenyl-11,12-dihydroindolo[2,3-a]carbazole, 12-(2-(4,6-diphenyl-1,3,5-triazin-2-yl)phenyl)-12H-benzofuro[2,3,a]carbazole, and 9-((4-(4,6-dipyridin-3-yl)-1,3,5-triazin-2-yl)phenyl)-9H-carbazole; 3-phenyl-4-(1'-naphthyl)-5-phenyl-1,2,triazole derivatives such as 4-triazole (TAZ), oxazole derivatives, oxadiazole derivatives such as 2-(4-biphenylyl)-5-(4-tert-butylphenyl-1,3,4-oxadiazole) (PBD), imidazole derivatives such as 2,2',2''-(1,3,5-bentriyl)-tris(1-phenyl-1-H-benzimidazole) (TPBI), naphthalene-1,4,5,8-tetracarboxylic dianhydride, 3, Aromatic carboxylic acid anhydrides such as 4,9,10-perylenetetracarboxylic dianhydride, aromatic imide compounds such as N,N'-dimethyl-3,4,9,10-perylenetetracarboxylic diimide, compounds having a carbonyl group such as isoindigo derivatives, 2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione derivatives (diketopyrrolopyrroles), and truxenone, naphtho[1,2-c:5,6-c']bis[1,2,5]thiadiazole, benzyl ether, compounds having a heterocycle containing a carbonyl group such as the compound represented by formula (30) described later; various metal complexes represented by bis[2-(2-hydroxyphenyl)benzothiazolato]zinc (Zn(BTZ)2) and tris(8-hydroxyquinolinato)aluminum (Alq3); Examples of the organic silane derivatives include silole derivatives such as diphenylsilole (PyPySPyPy), tris(2,4,6-trimethyl-3-(pyridin-3-yl)phenyl)borane (3TPYMB), and boron-containing compounds described in Japanese Patent Application No. 2012-228460, Japanese Patent Application No. 2015-503053, Japanese Patent Application No. 2015-053872, Japanese Patent Application No. 2015-081108, and Japanese Patent Application No. 2015-081109. One or more of these may be used. Moreover, the material of the light-emitting layer described later can also be used as the second material.
[0068] Among these second materials, it is more preferable to use a phosphine oxide derivative such as POPy2, a boron-containing compound such as the compounds represented by the following formulas (6) to (9), a metal complex such as Alq3, a pyridine derivative such as TmPhPyB, or a triazine derivative such as TmPhPyTz. Among these second materials, it is particularly preferable that the second material is a boron-containing compound or a triazine derivative. Note that n in formula (8) 1 represents an integer of 1 or greater.
[0069] [ka]
[0070] When a boron-containing compound is used as the second material having electron transport properties, a uniform organic thin film can be easily obtained by applying a coating composition containing a first material and a second material. Such a coating composition containing an electron-donating first material represented by the above general formula (1) and a second material transporting electrons is also one aspect of the present invention. In addition, a coating composition containing an electron-donating first material represented by the above general formula (1) and not containing a second material is also useful. Such a coating composition containing an electron-donating first material represented by the above general formula (1) is also one aspect of the present invention. In addition, boron-containing compounds and triazine derivatives have deep lowest unoccupied molecular orbital (LUMO) energies, making them suitable materials for the electron injection layer of organic electroluminescence devices. Therefore, organic thin films containing boron-containing compounds as the second material are particularly suitable for the electron injection layer of organic electroluminescence devices.
[0071] The ratio of the first material to the second material contained in the organic thin film of the present invention is not particularly limited and can be appropriately determined depending on the type of compound used in each of the first material and the second material. The ratio of the first material to the second material is preferably 0.1:99.9 to 20:1 in mass ratio (first material:second material). More preferably, it is 0.5:99.5 to 10:1. When the ratio is as above, the effect of improving the electron transport property and the electron injection property due to the inclusion of the first material and the second material in the organic thin film becomes significant.
[0072] The organic thin film in the present invention may be a single film containing the first material and the second material, or may be a laminated film of a film containing at least the first material and a film containing at least the second material. In the case of a laminated film, it may be a laminated film of a film containing only the first material and a film containing only the second material, or a laminated film of a film containing the first material and the second material and a film containing only one of the first material and the second material. In the case of a laminated film of a film containing the first material and the second material and a film containing only one of the first material and the second material, the film containing only one of the first material and the second material may contain either the first material or the second material, but it is preferable that it contains the second material. Furthermore, when such an organic thin film is used as a layer constituting an organic electroluminescence element, either the film containing the first material and the second material or the film containing only one of the first material and the second material may be on the cathode side, but it is preferable that the film containing only one of the first material and the second material is on the cathode side.
[0073] When the organic thin film in the present invention is a laminated film of a film containing a first material and a second material and a film containing only the first material, both of the two laminated films contain the first material, and the first materials contained in the two films may be the same or different. Similarly, when the organic thin film in the present invention is a laminated film of a film containing a first material and a second material and a film containing only the second material, the second material is contained in both of the two laminated films, and the second materials contained in the two films may be the same or different.
[0074] The organic thin film of the present invention may contain other components as long as it contains at least the first material and the second material, but the total proportion of the first material and the second material is preferably more than 95 mass % of the entire organic thin film, more preferably more than 99 mass %, and most preferably 100 mass %, i.e., the organic thin film is composed only of the first material and the second material.
[0075] In addition, it is one of the preferred embodiments of the present invention that the organic thin film in the present invention contains a metal oxide. The organic electroluminescent element of the present invention may contain a metal oxide layer. As described later, it has been reported that in both cases where a metal is formed on an organic thin film and where an organic thin film is formed on a cathode, the metal diffuses a distance of several nanometers toward the organic thin film. Therefore, when the organic electroluminescent element of the present invention uses a metal oxide as a material for the cathode or metal oxide layer, and the organic thin film of the present invention is formed adjacent to the metal oxide layer, the organic thin film contains a metal oxide. In this way, it is one of the preferred embodiments of the present invention that the organic thin film contains a metal oxide.
[0076] The first material alone can exhibit excellent electron injection properties. An organic thin film that contains such a first material but does not contain a second material also constitutes one aspect of the present invention. For this reason, an organic thin film of the present invention is an organic thin film containing at least a first material, and further contains a second material, and is a single film containing the first material and the second material, or a laminate film of a film containing the first material and a film containing the second material, can be said to be one of the preferred embodiments of the organic thin film of the present invention. In the organic thin film of the present invention that contains the first material but not the second material, the proportion of the first material is preferably more than 95 mass % of the entire organic thin film, more preferably more than 99 mass %, and most preferably 100 mass %, i.e., the organic thin film is composed only of the first material. In the following, a manufacturing method will be described for an organic thin film that is a single film containing a first material and a second material, or a laminated film of a film containing a first material and a film containing a second material. However, the manufacturing method, raw materials, etc. are similar for an organic thin film that contains only the first material and does not contain the second material, except that it does not contain the second material.
[0077] "Method of manufacturing organic thin films" Next, the method for producing an organic thin film of the present invention will be described with reference to examples. The organic thin film of the present invention includes a first material made of an electron-donating compound having a structure represented by the above general formula (1), and a second material that transports electrons. Both the first material and the second material have relatively large molecular weights, so that the organic thin film of the present invention can be formed not only by coating but also by vapor deposition. Therefore, there are few process restrictions when manufacturing an organic EL device including the organic thin film of the present invention, and it is easy to use it as a material for a layer that constitutes an organic EL device. When the organic thin film is produced by deposition, it can be produced by the same method as when other layers constituting the organic EL element are produced by deposition, and the first material and the second material may be simultaneously deposited or sequentially deposited. When deposited sequentially, either the first material or the second material may be deposited first. In addition, either one may be deposited first and then both may be co-deposited, or both may be co-deposited and then either one may be deposited. Such a method for producing an organic thin film including a step of simultaneously depositing the first material, which is a compound having a structure represented by the above general formula (1), and the second material transporting electrons on the surface on which the organic thin film is to be formed is one of the preferred embodiments of the method for producing an organic thin film of the present invention. In addition, a method for producing an organic thin film comprising a step of first depositing either a first material or a second material onto a surface on which an organic thin film is to be formed, and then depositing the other material or both of the materials, or a method for producing an organic thin film comprising a step of simultaneously depositing a first material and a second material onto a surface on which an organic thin film is to be formed, and then depositing either the first material or the second material onto the surface on which an organic thin film is to be formed, is also one of suitable embodiments of the method for producing an organic thin film of the present invention.
[0078] The organic thin film of the present invention can also be produced by coating. In this case, a coating composition containing the first material and the second material that transports electrons is prepared and the coating composition is applied, or a coating composition containing the first material and a coating composition containing the second material are prepared and applied in sequence to produce an organic thin film. When coating in sequence, either the coating composition containing the first material or the coating composition containing the second material may be applied first. Also, a coating composition containing only one of the materials may be applied, and then a coating composition containing both of these materials may be applied, or a coating composition containing only one of the materials may be applied, and then a coating composition containing both of these materials may be applied. Such a method for producing an organic thin film that includes a step of coating a coating composition containing a first material, which is a compound having a structure represented by the above general formula (1), and a second material that transports electrons on the surface on which the organic thin film is to be formed is one of the preferred embodiments of the method for producing an organic thin film of the present invention. Furthermore, a method for producing an organic thin film comprising a step of first applying either a coating composition containing only the first material or a coating composition containing only the second material onto a surface on which an organic thin film is to be formed, and a step of applying a coating composition containing the other or both of the materials onto the coating film formed by the step, or a method for producing an organic thin film comprising a step of applying a coating composition containing both the first material and the second material, and a step of applying a coating composition containing only either the first material or the second material onto the coating film formed by the step, is also one of the preferred embodiments of the method for producing an organic thin film of the present invention. In the following, a method for producing an organic thin film by preparing a coating composition containing a first material made of a compound having a structure represented by general formula (1) and a second material that transports electrons, and applying the coating composition will be described.
[0079] The coating composition can be obtained, for example, by a method in which a predetermined amount of each of the first material and the second material is fed into a solvent placed in a container, and the materials are stirred and dissolved. The solvent used to dissolve the first material and the second material may be, for example, an inorganic solvent, an organic solvent, or a mixed solvent containing these. Examples of inorganic solvents include nitric acid, sulfuric acid, ammonia, hydrogen peroxide, water, carbon disulfide, carbon tetrachloride, and ethylene carbonate.
[0080] Examples of organic solvents include ketone-based solvents such as methyl ethyl ketone (MEK), acetone, diethyl ketone, methyl isobutyl ketone (MIBK), methyl isopropyl ketone (MIPK), diisobutyl ketone, 3,5,5-trimethylcyclohexanone, diacetone alcohol, cyclopentanone, and cyclohexanone; alcohol-based solvents such as methanol, ethanol, isopropanol, ethylene glycol, diethylene glycol (DEG), and glycerin; ether-based solvents such as diethyl ether, diisopropyl ether, 1,2-dimethoxyethane (DME), 1,4-dioxane, tetrahydrofuran (THF), tetrahydropyran (THP), anisole, diethylene glycol dimethyl ether (diglyme), and diethylene glycol ethyl ether (carbitol); cellosolve-based solvents such as methyl cellosolve, ethyl cellosolve, and phenyl cellosolve; aliphatic hydrocarbon-based solvents such as hexane, pentane, heptane, and cyclohexane; toluene, xylene, benzene, and the like. Examples of the organic solvent include aromatic hydrocarbon solvents such as benzene, aromatic heterocyclic compound solvents such as pyridine, pyrazine, furan, pyrrole, thiophene, and methylpyrrolidone, amide solvents such as N,N-dimethylformamide (DMF) and N,N-dimethylacetamide (DMA), halogen compound solvents such as chlorobenzene, dichloromethane, chloroform, and 1,2-dichloroethane, ester solvents such as ethyl acetate, methyl acetate, and ethyl formate, sulfur compound solvents such as dimethyl sulfoxide (DMSO) and sulfolane, nitrile solvents such as acetonitrile, propionitrile, and acrylonitrile, and organic acid solvents such as formic acid, acetic acid, trichloroacetic acid, and trifluoroacetic acid. Among these, ketone solvents such as methyl ethyl ketone (MEK), acetone, diethyl ketone, methyl isobutyl ketone (MIBK), methyl isopropyl ketone (MIPK), diisobutyl ketone, 3,5,5-trimethylcyclohexanone, diacetone alcohol, and cyclopentanone are preferred.
[0081] Examples of methods that can be used for applying the coating composition containing the first material and the second material include various application methods such as spin coating, casting, microgravure coating, gravure coating, bar coating, roll coating, wire bar coating, dip coating, spray coating, screen printing, flexographic printing, offset printing, and inkjet printing.
[0082] After the coating composition is applied in this manner, it is preferable to carry out an annealing treatment. The annealing treatment is preferably carried out at 70 to 200°C for 0.1 to 5 hours in a nitrogen atmosphere or in the air. By carrying out such an annealing treatment, the solvent can be evaporated to form an organic thin film.
[0083] In addition, an organic thin film containing the electron-donating first material represented by the above general formula (1) and not containing the second material is also useful as a material for an organic EL device, etc. Such a method for producing an organic thin film including a step of forming a film containing the electron-donating first material represented by the above general formula (1) on a surface to be formed is also one aspect of the present invention, and including a step of forming a film containing the electron-donating first material represented by the above general formula (1) on a surface to be formed containing the second material is one of the preferred embodiments of the method for producing an organic thin film.
[0084] "Organic EL element" The present invention also relates to an organic electroluminescence (EL) device having a light-emitting layer between a cathode and an anode, and further comprising any one of a layer of the organic thin film of the present invention, a layer of a laminate film of the organic thin film layer and a metal oxide layer, or a layer containing the material for organic electroluminescence devices of the present invention. The organic thin film layer, the laminated film layer of the organic thin film layer and a metal oxide layer, and the layer containing the material for an organic electroluminescence device of the present invention may be located between the cathode and the light-emitting layer or between the anode and the light-emitting layer in the organic EL device of the present invention, but is preferably located between the cathode and the light-emitting layer. In addition, the layer containing the material for an organic electroluminescence device of the present invention may contain other components as long as it contains a compound having a structure represented by the above-mentioned general formula (1). However, it is preferable that the layer is composed only of a compound having a structure represented by the general formula (1).
[0085] The present invention also relates to an organic electroluminescence (EL) element having a light-emitting layer between a cathode and an anode, which includes a layer of the organic thin film of the present invention or a layer of a laminate film of the organic thin film and a metal oxide layer between the cathode and the anode, and the light-emitting layer includes a second material.The present invention also relates to an organic electroluminescence (EL) element including a layer of the organic thin film of the present invention or a layer of a laminate film of the organic thin film and a metal oxide layer between the cathode and the anode, in which the organic thin film or the laminate film is adjacent to the light-emitting layer and includes a material used in the light-emitting layer as the second material, or the film including the second material among the organic thin film or the laminate film is the light-emitting layer. The compound represented by the above general formula (1), which is the first material of the present invention, has extremely excellent electron injection properties, and is therefore capable of directly injecting electrons into the light-emitting material and host material used in the light-emitting layer. Therefore, by using the first material of the present invention in the electron injection layer, it is possible to reduce the number of materials used and the number of layers to be laminated, thereby making it possible to provide an organic EL device with a simpler structure. That is, when the element using the organic thin film or laminated film of the present invention is an element in which a layer containing a first material, a layer containing a second material, and a light-emitting layer are adjacent to each other, and even when the light-emitting material or host material used in the light-emitting layer is used as the material of the layer containing the second material, it is possible to inject electrons from the layer containing the first material, and in this way, the layer containing the second material and the light-emitting layer can be formed using a common material, so that the number of materials used can be reduced. In this case, the second material may be either a light-emitting material or a host material of the light-emitting layer. In addition, when the layer containing the second material is formed using a light-emitting material or a host material of the light-emitting layer and used as the light-emitting layer, it becomes unnecessary to provide a separate light-emitting layer, so that it is possible to reduce the number of layers to be laminated and to obtain an organic EL element with a simpler structure. Furthermore, if the second material is used as the material of the layer adjacent to the anode side of the light-emitting layer, it is possible to further reduce the number of layers to be laminated and to obtain an organic EL element with a simpler structure. Therefore, the light-emitting layer containing the second material and the layer containing the second material between the anode and the light-emitting layer are both preferred embodiments of the organic electroluminescence (EL) element of the present invention.
[0086] Next, the organic EL device of the present invention will be described in detail with reference to examples. Fig. 4 is a schematic cross-sectional view for explaining one example of the organic EL element of the present invention. The organic EL element 1 of this embodiment shown in Fig. 4 has an emitting layer 6 between a cathode 3 and an anode 9. The organic EL element 1 shown in Fig. 4 has an electron injection layer 5 made of the organic thin film of the present invention or the material for organic electroluminescence devices of the present invention between the cathode 3 and the emitting layer 6. In addition, an oxide layer 4 is provided between the cathode 3 and the electron injection layer 5 made of the organic thin film of the present invention or the material for organic electroluminescence devices of the present invention, and the oxide layer 4 is adjacent to the electron injection layer 5. All of these are suitable embodiments of the organic EL element of the present invention. The organic EL device 1 of the present embodiment has a laminated structure in which a cathode 3, an inorganic oxide layer 4, an electron injection layer 5, an electron transport layer 10, a light-emitting layer 6, a hole transport layer 7, a hole injection layer 8, and an anode 9 are formed in this order on a substrate 2. Thus, having an inorganic oxide layer between the cathode and the layer of the organic thin film or the layer of the material for organic electroluminescence devices of the present invention is one of the preferred embodiments of the organic EL device of the present invention.
[0087] The organic EL element 1 shown in Fig. 4 is an organic EL element having an inverted structure in which a cathode 3 is disposed between a substrate 2 and a light-emitting layer 6. The organic EL element 1 shown in Fig. 4 is an organic-inorganic hybrid organic electroluminescent element (HOILED element) in which a part of the layers constituting the organic EL element (at least the inorganic oxide layer 4) is formed using an inorganic compound. The organic EL element 1 shown in FIG. 4 may be of a top emission type in which light is extracted from the side opposite to the substrate 2, or of a bottom emission type in which light is extracted from the substrate 2 side.
[0088] FIG. 5 is a diagram showing an example of the device configuration when the organic EL device of the present invention is an organic EL device having a forward structure in which a light-emitting layer 6 is disposed between a substrate 2 and a cathode 3. In FIG. As described above, the compound represented by the general formula (1) of the present invention has an extremely excellent electron injection property, and therefore can directly inject electrons into the material used in the light-emitting layer. Therefore, when using a material for an organic EL device containing the compound represented by the general formula (1) of the present invention, even if an organic EL device having a simple structure is formed by forming an electron transport layer 10 from a material used in the light-emitting layer and using the same material for the light-emitting layer 6 and the electron transport layer 10 as shown in FIG. 6, it is possible to operate at a low driving voltage by using the compound represented by the general formula (1) in the electron injection layer 5. In this case, it is possible to reduce the number of materials used as compared with a typical organic EL device. Here, if the electron transport layer 10 contains the second material of the present invention, it can be said that the organic EL device uses the organic thin film of the present invention. Furthermore, since holes can be relatively easily injected from the hole injection layer 8 into the material used in the light emitting layer, when the material for an organic EL device containing the compound represented by the general formula (1) of the present invention is used in the electron injection layer 5, it is possible to operate at a low driving voltage even if the material used in the light emitting layer is used in the hole transport layer 7, as shown in Fig. 7. In this case, it is possible to reduce the number of materials used by at least two compared to a typical organic EL device. Here, if the electron transport layer 10 contains the second material of the present invention, it can be said that the organic EL device uses the organic thin film of the present invention. Although the organic EL element having a forward structure has been described here, the organic EL element of the present invention in which the light-emitting layer contains the second material is not limited to the forward structure, and may have an inverted structure.
[0089] In the following embodiment, an organic EL element 1 having an inverted structure is taken as an example for explanation, but the organic EL element of the present invention may have a forward structure in which an anode is disposed between a substrate and an emitting layer. When the organic EL element of the present invention has a forward structure, the organic thin film is disposed between the cathode and the emitting layer, as in the case of the inverted structure. In the case of the inverted structure, the electron injection layer is sometimes called an organic buffer layer. The materials, thicknesses, and sealing of each layer constituting the organic EL element 1 described below are the same for an organic EL element having a forward structure, except for the materials of the cathode and anode described later. All of the contents described below can be applied to an organic EL element having a forward structure.
[0090] "substrate" The material of the substrate 2 may be a resin material, a glass material, or the like. Examples of the resin material used for the substrate 2 include polyethylene terephthalate, polyethylene naphthalate, polypropylene, cycloolefin polymer, polyamide, polyethersulfone, polymethyl methacrylate, polycarbonate, polyarylate, etc. When a resin material is used as the material for the substrate 2, it is preferable because an organic EL element 1 having excellent flexibility can be obtained. Examples of the glass material used for the substrate 2 include quartz glass and soda glass.
[0091] When the organic EL element 1 is of a bottom emission type, the material of the substrate 2 is a transparent substrate. When the organic EL element 1 is of a top emission type, not only a transparent substrate but also an opaque substrate may be used as the material of the substrate 2. Examples of opaque substrates include a substrate made of a ceramic material such as alumina, a substrate in which an oxide film (insulating film) is formed on the surface of a metal plate such as stainless steel, and a substrate made of a resin material.
[0092] The average thickness of the substrate 2 can be determined depending on the material of the substrate 2, and is preferably 0.1 to 30 mm, and more preferably 0.1 to 10 mm. The average thickness of the substrate 2 can be measured with a digital multimeter and a vernier caliper.
[0093] "cathode" The cathode 3 is formed on and in direct contact with the substrate 2 . Examples of materials for the cathode 3 include oxides such as ITO (indium tin oxide), IZO (indium zinc oxide), FTO (fluorine tin oxide), In3O3, SnO2, Sb-containing SnO2, and Al-containing ZnO, as well as conductive materials such as Al, Au, Pt, Ag, Cu, and alloys containing these. Among these, it is preferable to use ITO, IZO, FTO, or Al as the material for the cathode 3. The average thickness of the cathode 3 is not particularly limited, but is preferably from 10 to 500 nm, and more preferably from 100 to 200 nm. The average thickness of the cathode 3 can be measured by a stylus step gauge or spectroscopic ellipsometry. These materials can be used as the anode material when the organic EL device of the present invention has a forward structure in which the anode is disposed between the substrate and the light-emitting layer. In this case, the average thickness of the anode is preferably the same as that of the cathode 3.
[0094] "Oxide layer" The inorganic oxide layer 4 functions as an electron injection layer and / or a cathode. The oxide layer 4 is a semiconductor or insulator laminated thin film layer. Specifically, the oxide layer 4 may be any of a layer made of a single metal oxide, a layer made of a mixture of two or more metal oxides and a layer made of a single metal oxide, or a layer made of a mixture of two or more metal oxides. Metal elements constituting the metal oxide that forms the oxide layer 4 include magnesium, calcium, strontium, barium, titanium, zirconium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, manganese, indium, gallium, iron, cobalt, nickel, copper, zinc, cadmium, aluminum, and silicon.
[0095] When the oxide layer 4 includes a layer containing a mixture of two or more types of metal oxides, it is preferable that at least one of the metal elements constituting the metal oxide is magnesium, aluminum, calcium, zirconium, hafnium, silicon, titanium, or zinc. When the oxide layer 4 is a layer made of a simple metal oxide, it is preferably a layer made of a metal oxide selected from the group consisting of magnesium oxide, aluminum oxide, zirconium oxide, hafnium oxide, silicon oxide, titanium oxide, and zinc oxide.
[0096] When the oxide layer 4 is a layer obtained by laminating either or both of a layer of a mixture of two or more kinds of metal oxides and a layer made of a single metal oxide, or a layer obtained by laminating two or more kinds of metal oxides, examples of the oxide layer 4 include a layer obtained by laminating and / or mixing a combination of two kinds of metal oxides selected from titanium oxide / zinc oxide, titanium oxide / magnesium oxide, titanium oxide / zirconium oxide, titanium oxide / aluminum oxide, titanium oxide / hafnium oxide, titanium oxide / silicon oxide, zinc oxide / magnesium oxide, zinc oxide / zirconium oxide, zinc oxide / hafnium oxide, zinc oxide / silicon oxide, and calcium oxide / aluminum oxide, a layer obtained by laminating and / or mixing a combination of three kinds of metal oxides selected from titanium oxide / zinc oxide / magnesium oxide, titanium oxide / zinc oxide / zirconium oxide, titanium oxide / zinc oxide / aluminum oxide, titanium oxide / zinc oxide / hafnium oxide, titanium oxide / zinc oxide / silicon oxide, and indium oxide / gallium oxide / zinc oxide.
[0097] The oxide layer 4 may contain IGZO (indium gallium zinc oxide), which is an oxide semiconductor exhibiting good characteristics as a special composition, and / or 12CaO·7Al2O3, which is an electride. The average thickness of the oxide layer 4 is not particularly limited, but is preferably 1 to 1000 nm, and more preferably 2 to 100 nm. The average thickness of the oxide layer 4 can be measured by a stylus step gauge or spectroscopic ellipsometry.
[0098] "Electron injection layer" The electron injection layer 5 serves to improve the speed and electron transport properties of the electron injection from the cathode to the light emitting layer 6. The electron injection layer 5 is made of the above-mentioned organic thin film. The average thickness of the electron injection layer 5 is preferably 0.5 to 100 nm, more preferably 1 to 100 nm, further preferably 5 to 100 nm, and particularly preferably 10 to 50 nm. When the average thickness of the electron injection layer 5 is 0.5 nm or more, the electron injection layer 5 having a smooth surface can be obtained by forming the electron injection layer 5 using either a method of applying a coating composition containing the first material and the second material, or a method of applying a coating composition containing the first material and a coating composition containing the second material in sequence. Alternatively, the electron injection layer 5 made of the first material and the second material can be obtained by co-deposition using a vacuum deposition method. In addition, when the average thickness of the electron injection layer 5 is 100 nm or less, the increase in the driving voltage of the organic EL device 1 due to the provision of the electron injection layer 5 can be sufficiently suppressed. In addition, when forming a film containing the first material and the second material, any of the structures shown in Figures 8-1 to 14-1 (Figures 8-2 to 14-2 in the case of a normal structure) may be used. For example, the film may be made of one layer, and the entire film may constitute the electron injection layer (Figures 8-1 and 8-2), or one of the film made of only the first material and the film made of only the second material may be formed adjacent to the cathode or oxide, and the other film may be formed adjacent to that film (Figures 9-1, 9-2, Figures 10-1 and 10-2). In addition, a film containing the first material and the second material may be formed adjacent to the cathode or oxide, and a film made of only the second material may be formed adjacent to that film (Figures 11-1 and 11-2), or a film made of only the second material, not including the first material, may be formed adjacent to the cathode or oxide, and a film containing the first material and the second material may be formed adjacent to that film (Figures 12-1 and 12-2). Furthermore, the film may be formed to have a three-layer structure (Figures 13-1, 13-2, Figures 14-1, 14-2) in which a film consisting of only the first material or a film containing the first material and the second material is sandwiched between films consisting of only the second material. The present invention includes any of the films having the structures shown in Figures 8-1 to 14-1 and 8-2 to 14-2. When the second material is contained in two adjacent films or two or more films of a three-layer structure film as shown in Figures 11-1 to 14-1 and 11-2 to 14-2, the second materials contained in these two or more films may be the same or different. Furthermore, among these structures, for the structures of Figures 9-1 and 9-2, Figures 10-1 and 10-2, and Figures 13-1 and 13-2 which include a layer consisting only of the first material, the layer consisting only of the first material can also be regarded as a layer formed from the organic thin film of the present invention (an organic thin film which includes only the first material and does not include the second material). The average thickness of the electron injection layer 5 can be measured by, for example, a stylus step gauge or spectroscopic ellipsometry.
[0099] As described above, since the first material, which is an electron-donating organic material, has the ability to generate negative charges in other materials, it is preferable that the first material is present in greater amounts on the cathode 3 or oxide layer 4 side in order to sufficiently promote electron injection from the cathode 3 or oxide layer 4. However, since this negative charge can contribute to the promotion of electron injection even if it is not in direct contact with the oxide or cathode, the effect of electron injection due to the presence of the first material can be obtained even in the laminated structures shown in Figures 9-1 and 9-2, Figures 12-1 and 12-2, Figures 13-1 and 13-2, Figures 14-1 and 14-2. It has been reported that in both cases where a metal is deposited on an organic thin film and where an organic thin film is deposited on a cathode, the metal diffuses a distance of several nanometers toward the organic thin film (see Lee, JH, Yi, Y. & Moon, DW Direct evidence of Al diffusion into tris-(8-hydroquinoline) aluminum layer: medium energy ion scattering analysis. Applied Physics Letters 93, doi:10.1063 / 1.3002290 (2008) and Non-Patent Document 12). Therefore, even in a laminated structure in which the second material is present on the cathode 3 side, the effect of electron injection due to a coordination reaction with the first material by the diffusion of the metal can be obtained. In other words, the effect of the present invention can be obtained even if the first material is not directly formed on the cathode 3 or the oxide layer 4.
[0100] As described above, the first material, which is an electron-donating organic material, is a material capable of generating negative charges in other materials, and in order to fully exert the effect of the organic thin film of the present invention, it is preferable that the organic thin film of the present invention forms a layer containing the first material adjacent to the cathode or the oxide layer (Figures 8-1, 8-2, 10-1, 10-2, 11-1, 11-2), but as shown in Figures 9-1, 9-2, 12-1, 12-2, 13-1, 13-2, 14-1, 14-2, the effect can be obtained even if the layer containing the first material is not directly formed adjacent to the cathode or the oxide layer. Any of the films of the laminated structure obtained in this way, that is, a laminated film consisting of an oxide layer and a layer of the organic thin film of the present invention formed adjacent to the oxide layer, and a laminated film consisting of a cathode and a layer of the organic thin film of the present invention formed adjacent to the cathode, are also one of the present inventions. When an organic EL element includes an oxide layer and a layer of the organic thin film of the present invention formed adjacent to the oxide layer in a laminate structure, or when an organic EL element includes a cathode and a layer of the organic thin film of the present invention formed adjacent to the cathode in a laminate structure, the organic EL element can be said to be configured to include the laminate film of the present invention. An organic EL element configured to include such a laminate film of the present invention is also one aspect of the present invention.
[0101] The organic EL element of the present invention may have a laminated film as shown in Figures 11-1, 11-2, 12-1, 12-2, or 14-1, 14-2 as an electron injection layer. In other words, having a laminated film of a film containing the first material and the second material and a film containing the second material between the cathode and the light-emitting layer is one of the preferred embodiments of the organic EL element of the present invention. In this case, either an organic EL element having a layer containing the second material between the light-emitting layer and the film containing the first material and the second material, or an organic EL element having a layer containing the second material between the cathode and the film containing the first material and the second material, is one of the preferred embodiments of the organic EL element of the present invention.
[0102] "Electron transport material" The electron transport layer 10 may be made of any material that can be commonly used as a material for an electron transport layer. Specifically, the material of the electron transport layer 10 may be a phosphine oxide derivative such as phenyl-dipyrenylphosphine oxide (POPy2), a pyridine derivative such as tris-1,3,5-(3'-(pyridin-3''-yl)phenyl)benzene (TmPhPyB), a quinoline derivative such as (2-(3-(9-carbazolyl)phenyl)quinoline (mCQ)), a pyrimidine derivative such as 2-phenyl-4,6-bis(3,5-dipyridylphenyl)pyrimidine (BPyPPM), a pyrazine derivative, or a bathophenanthroline (BPhen). phenanthroline derivatives such as 2,4-bis(4-biphenyl)-6-(4'-(2-pyridinyl)-4-biphenyl)-[1,3,5]triazine (MPT), triazole derivatives such as 3-phenyl-4-(1'-naphthyl)-5-phenyl-1,2,4-triazole (TAZ), oxazole derivatives, oxadiazole derivatives such as 2-(4-biphenylyl)-5-(4-tert-butylphenyl-1,3,4-oxadiazole) (PBD), 2,2',2''-(1,3,5-pentyl)- Imidazole derivatives such as tris(1-phenyl-1-H-benzimidazole) (TPBI), aromatic carboxylic anhydrides such as naphthalene-1,4,5,8-tetracarboxylic dianhydride and 3,4,9,10-perylenetetracarboxylic dianhydride, aromatic imide compounds such as N,N'-dimethyl-3,4,9,10-perylenetetracarboxylic dianhydride, compounds with carbonyl groups such as isoindigo derivatives, 2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione derivatives (diketopyrrolopyrroles), and truxenone, naphtho[ 1,2,5-thiadiazole derivatives such as 1,2-c:5,6-c']bis[1,2,5]thiadiazole and benzo[c][1,2,5]thiadiazole; various metal complexes such as bis[2-(2-hydroxyphenyl)benzothiazolato]zinc (Zn(BTZ)2) and tris(8-hydroxyquinolinato)aluminum (Alq3); organic silane derivatives such as silole derivatives such as 2,5-bis(6'-(2',2''-bipyridyl))-1,1-dimethyl-3,4-diphenylsilole (PyPySPyPy);6-trimethyl-3-(pyridin-3-yl)phenyl)borane (3TPYMB) and boron-containing compounds described in Japanese Patent Application No. 2012-228460, Japanese Patent Application No. 2015-503053, Japanese Patent Application No. 2015-053872, Japanese Patent Application No. 2015-081108 and Japanese Patent Application No. 2015-081109, and the like, and one or more of these can be used. Among these materials for the electron transport layer 10, it is particularly preferable to use a phosphine oxide derivative such as POPy2, a metal complex such as Alq3, or a pyridine derivative such as TmPhPyB. As in the case of an organic EL element in which a layer containing the above-mentioned second material is formed using the light-emitting material or host material used in the light-emitting layer, the organic EL element of the present invention does not need to have an electron-transport layer using the above-mentioned electron-transport material in the laminate structure as long as the organic EL element exhibits its function.
[0103] When the organic EL device of the present invention uses an organic thin film containing only the first material as the electron injection layer, the second material of the organic thin film of the present invention can be used as the material of the electron transport layer 10 . When the organic EL device of the present invention uses a single film containing the first material and the second material as the electron injection layer 5, the electron transport layer 10 may be omitted.
[0104] The average thickness of the electron transport layer 10 is not particularly limited, but is preferably from 10 to 150 nm, and more preferably from 20 to 100 nm. The average thickness of the electron transport layer 10 can be measured by a stylus step gauge or spectroscopic ellipsometry.
[0105] "Light-emitting layer" The material for forming the light-emitting layer 6 may be any material that can be normally used as the material for the light-emitting layer 6, or a mixture of these materials may be used. Specifically, for example, the light-emitting layer 6 may contain bis[2-(2-benzothiazolyl)phenolato]zinc(II) (Zn(BTZ)2) and tris[1-phenylisoquinoline]iridium(III) (Ir(piq)3). The material forming the light-emitting layer 6 may be a low molecular weight compound or a high molecular weight compound. In the present invention, the low molecular weight material means a material that is not a high molecular weight material (polymer), and does not necessarily mean an organic compound with a low molecular weight.
[0106] Examples of the polymeric material for forming the light-emitting layer 6 include polyacetylene compounds such as trans-polyacetylene, cis-polyacetylene, poly(di-phenylacetylene) (PDPA), and poly(alkylphenylacetylene) (PAPA); poly(para-phenylenevinylene) (PPV), poly(2,5-dialkoxy-para-phenylenevinylene) (RO-PPV), cyano-substituted-poly(para-phenylenevinylene) (CN-PPV), poly(2-dimethylphenylacetylene) (PDPA), poly(di ... poly(p-phenylene vinylene)-based compounds such as poly(2-methoxy,5-(2'-ethylhexoxy)-p-phenylene vinylene) (MEH-PPV); polythiophene-based compounds such as poly(3-alkylthiophene) (PAT) and poly(oxypropylene) triol (POPT); poly(9,9-dialkylfluorene) (PDAF), poly(dioctylfluorene) -alto-benzothiadiazole) (F8BT), α,ω-bis[N,N'-di(methylphenyl)aminophenyl]-poly[9,9-bis(2-ethylhexyl)fluorene-2,7-diyl] (PF2 / 6am4), poly(9,9-dioctyl-2,7-divinylenefluorenyl-ortho-co(anthracene-9,10-diyl); poly(para-phenylene) (PPP), poly(1,5-dialkoxy- ... Examples of such compounds include polyparaphenylene compounds such as poly(paraphenylene) (RO-PPP); polycarbazole compounds such as poly(N-vinylcarbazole) (PVK); polysilane compounds such as poly(methylphenylsilane) (PMPS), poly(naphthylphenylsilane) (PNPS), and poly(biphenylylphenylsilane) (PBPS); and boron compound-based polymer materials described in Japanese Patent Application Nos. 2010-230995 and 2011-6457.
[0107] Examples of low molecular weight materials for forming the light emitting layer 6 include three-coordinate iridium complexes having 2,2'-bipyridine-4,4'-dicarboxylic acid as a ligand, such as fac-tris(2-phenylpyridine)iridium (Ir(ppy)3), fac-tris(3-methyl-2-phenylpyridinato-N,C2'-)iridium(III) (Ir(mppy)3), 8-hydroxyquinoline aluminum (Alq3), tris(4-methyl-8-quinolinolato)aluminum(III) (Almq3), 8-hydroxyquinoline zinc (Znq2), (1, Various metal complexes such as 10-phenanthroline)-tris-(4,4,4-trifluoro-1-(2-thienyl)-butane-1,3-dionate) europium(III) (Eu(TTA)3(phen)), 2,3,7,8,12,13,17,18-octaethyl-21H,23H-porphine platinum(II); benzene-based compounds such as distyrylbenzene (DSB) and diaminodistyrylbenzene (DADSB); naphthalene-based compounds such as naphthalene and Nile Red; phenanthrene-based compounds such as phenanthrene chrysene, chrysene-based compounds such as 6-nitrochrysene; perylene, perylene-based compounds such as N,N'-bis(2,5-di-t-butylphenyl)-3,4,9,10-perylene-di-carboximide (BPPC); coronene-based compounds such as coronene; anthracene, bisstyryl anthracene, anthracene-based compounds such as (9,10-bis(4-(9H-carbazol-9-yl)-2,6-dimethylphenyl))-9,10-diboraanthracene (CzDBA) represented by the formula (31) described later; pyrene, pyrene pyran compounds such as 4-(di-cyanomethylene)-2-methyl-6-(para-dimethylaminostyryl)-4H-pyran (DCM); acridine compounds such as acridine; stilbene compounds such as stilbene; thiophene compounds such as 2,5-dibenzoxazolethiophene; benzoxazole compounds such as benzoxazole; benzimidazole compounds such as benzimidazole; benzothiazole compounds such as 2,2'-(para-phenylenedivinylene)-bisbenzothiazole;Butadiene compounds such as bistyryl (1,4-diphenyl-1,3-butadiene) and tetraphenylbutadiene; Naphthalimide compounds such as naphthalimide; Coumarin compounds such as coumarin; Perinone compounds such as perinone; Oxadiazole compounds such as oxadiazole; Aldazine compounds; Cyclopentadiene compounds such as 1,2,3,4,5-pentaphenyl-1,3-cyclopentadiene (PPCP); Quinacridone compounds such as quinacridone and quinacridone red; Pyridine compounds such as pyrrolopyridine and thiadiazolopyridine triazine compounds such as 2,4-diphenyl-6-bis((12-phenylindolo)[2,3-a]carbazol-11-yl)-1,3,5-triazine (DIC-TRZ) represented by formula (26) described later; spiro compounds such as 2,2',7,7'-tetraphenyl-9,9'-spirobifluorene; metal or metal-free phthalocyanine compounds such as phthalocyanine (H2Pc) and copper phthalocyanine; and boron compound materials described in JP-A-2009-155325, JP-A-2011-184430 and JP-A-2011-6458. Examples of the host material for the light-emitting layer include carbazole compounds such as 4,4'-bis(9H-carbazol-9-yl)biphenyl (CPB); silicon compounds; phenanthroline compounds; and triphenylene compounds.
[0108] The average thickness of the light-emitting layer 6 is not particularly limited, but is preferably from 10 to 150 nm, and more preferably from 20 to 100 nm. The average thickness of the light-emitting layer 6 may be measured by a stylus-type step gauge, or may be measured by a quartz crystal thickness gauge during the deposition of the light-emitting layer 6.
[0109] "Hole transport layer" As the hole transporting organic material used in the hole transport layer 7, various p-type polymeric materials (organic polymers) and various p-type low molecular weight materials can be used alone or in combination. Specifically, examples of the material for the hole transport layer 7 include N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4,4'-diamine (α-NPD), N4,N4'-bis(dibenzo[b,d]thiophen-4-yl)-N4,N4'-diphenylbiphenyl-4,4'-diamine (DBTPB), N3,N3'''-bis(dibenzo[b,d]thiophen-4-yl)-N3,N3'''-diphenyl-[1,1':2',1'':2'',1'''-quaternary Examples of the material for the hole transport layer 7 include poly(phenyl)-3,3'''-diamine (4DBTP3Q), polyarylamine, fluorene-arylamine copolymer, fluorene-bithiophene copolymer, poly(N-vinylcarbazole), polyvinylpyrene, polyvinylanthracene, polythiophene, polyalkylthiophene, polyhexylthiophene, poly(p-phenylenevinylene), polytinylenevinylene, pyrene formaldehyde resin, ethylcarbazole formaldehyde resin or derivatives thereof. These materials for the hole transport layer 7 can also be used as a mixture with other compounds. As an example, a mixture containing polythiophene used as a material for the hole transport layer 7 includes poly(3,4-ethylenedioxythiophene / styrenesulfonic acid) (PEDOT / PSS), etc. As described above, since holes can be relatively easily injected from the hole injection layer into the material used in the light emitting layer, the organic EL device of the present invention can operate at a low driving voltage even if the material used in the light emitting layer is used in the hole transport layer. Therefore, the organic EL device of the present invention does not need to have a hole transport layer using the hole transport material as described above.
[0110] The average thickness of the hole transport layer 7 is not particularly limited, but is preferably 10 to 150 nm, and more preferably 20 to 100 nm. The average thickness of the hole transport layer 7 can be measured by, for example, a stylus step gauge or spectroscopic ellipsometry.
[0111] "Hole injection layer" The hole injection layer 8 may be made of an inorganic material or an organic material. Inorganic materials are more stable than organic materials, and therefore tend to have high resistance to oxygen and water compared to the case where an organic material is used. The inorganic material is not particularly limited, but for example, one or more metal oxides such as vanadium oxide (V2O5), molybdenum oxide (MoO3), and ruthenium oxide (RuO2) can be used. Examples of organic materials that can be used include low molecular weight materials such as dipyrazino[2,3-f:2',3'-h]quinoxaline-2,3,6,7,10,11-hexacarbonitrile (HAT-CN), 2,3,5,6-tetrafluoro-7,7,8,8-tetracyano-quinodimethane (F4-TCNQ), and fullerene, as well as poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate (PEDOT:PSS).
[0112] The average thickness of the hole injection layer 8 is not particularly limited, but is preferably 1 to 1000 nm, and more preferably 5 to 50 nm. The average thickness of the hole injection layer 8 can be measured during deposition by a quartz crystal thickness gauge, a stylus step gauge, or spectroscopic ellipsometry.
[0113] "anode" Examples of materials used for the anode 9 include ITO, IZO, Au, Pt, Ag, Cu, Al, and alloys containing these. Among these, it is preferable to use ITO, IZO, Au, Ag, or Al as the material for the anode 9. The average thickness of the anode 9 is not particularly limited, but is preferably 10 to 1000 nm, and more preferably 30 to 150 nm. Even when an opaque material is used as the material for the anode 9, by setting the average thickness to, for example, about 10 to 30 nm, the anode can be used as a transparent anode in a top-emission organic EL device. The average thickness of the anode 9 can be measured by a quartz crystal film thickness meter during the deposition of the anode 9 . Any of these materials with Mg added can be used as the material for the cathode when the organic EL device of the present invention has a normal structure. In this case, the average thickness of the cathode is preferably the same as that of the anode 9.
[0114] "Sealing" The organic EL element 1 shown in FIG. 4 may be sealed, if necessary. For example, the organic EL element 1 shown in Fig. 4 may be sealed with a sealing container (not shown) having a concave space for accommodating the organic EL element 1, and an adhesive for bonding the edge of the sealing container to the substrate 2. Alternatively, the organic EL element 1 may be accommodated in a sealing container, and sealed by filling it with a sealant made of an ultraviolet (UV) curable resin or the like. Alternatively, for example, the organic EL element 1 shown in Fig. 4 may be sealed with a sealing member made of a plate member (not shown) arranged on the anode 9 and a frame member (not shown) arranged along the edge of the plate member on the side facing the anode 9, and an adhesive for bonding between the plate member and the frame member and between the frame member and the substrate 2.
[0115] When the organic EL element 1 is sealed using a sealing container or a sealing member, a desiccant that absorbs moisture may be placed inside the sealing container or the sealing member. A material that absorbs moisture may be used as the sealing container or the sealing member. A space may be formed inside the sealed sealing container or the sealing member.
[0116] Resin materials, glass materials, etc. can be used as the material for the sealing container or sealing member used to seal the organic EL element 1 shown in Fig. 4. Examples of the resin materials and glass materials used for the sealing container or sealing member include the same materials as those used for the substrate 2.
[0117] In the organic EL device 1 of this embodiment, when an electron injection layer is formed using an organic thin film made of a first material, which is an electron donating organic material represented by the above general formula (1), and a second material made of a boron-containing compound represented by the above formula (6), excellent durability can be obtained compared to, for example, a case in which an alkali metal, which is a material unstable in the atmosphere, is used as the electron injection layer. Therefore, when the water vapor transmission rate of the sealing container or sealing member is 10 -4 ~10 -3 Order (g / m 2 / day), deterioration of the organic EL element 1 can be sufficiently suppressed. -3 Order (g / m 2 It is possible to use a resin material with a thermal expansion coefficient of about 100 / day or less, and thus it is possible to realize an organic EL element 1 with excellent flexibility.
[0118] "Manufacturing method for organic EL elements" Next, as an example of a method for manufacturing the organic EL element of the present invention, a method for manufacturing the organic EL element 1 having an inverted structure shown in FIG. 4 will be described. To manufacture the organic EL element 1 shown in FIG. 4, first, the cathode 3 is formed on the substrate 2 . The cathode 3 can be formed by a sputtering method, a vacuum deposition method, a sol-gel method, a spray pyrolysis (SPD) method, an atomic layer deposition (ALD) method, a vapor phase deposition method, a liquid phase deposition method, etc. The cathode 3 may be formed by bonding a metal foil.
[0119] Next, an inorganic oxide layer 4 is formed on the cathode 3 . The oxide layer 4 is formed by using, for example, a spray pyrolysis method, a sol-gel method, a sputtering method, a vacuum deposition method, etc. The surface of the oxide layer 4 thus formed may not be smooth but may have projections and recesses.
[0120] Next, the electron injection layer 5 is formed on the oxide layer 4 . The electron injection layer 5 can be formed by the above-mentioned method for producing an organic thin film.
[0121] Next, on the electron injection layer 5, the electron transport layer 10, the light emitting layer 6, and the hole transport layer 7 are formed in this order. The methods for forming the electron transport layer 10, the light emitting layer 6, and the hole transport layer 7 are not particularly limited, and various conventionally known formation methods can be used appropriately in accordance with the characteristics of the materials used for the electron transport layer 10, the light emitting layer 6, and the hole transport layer 7, respectively.
[0122] Specifically, methods for forming the electron transport layer 10, the light emitting layer 6, and the hole transport layer 7 include a coating method for coating an organic compound solution containing an organic compound that will become the electron transport layer 10, the light emitting layer 6, and the hole transport layer 7, a vacuum deposition method, and an ESDUS (Evaporative Spray Deposition from Ultra-dilute Solution) method. Among these methods for forming the electron transport layer 10, the light emitting layer 6, and the hole transport layer 7, it is particularly preferable to use the coating method. Note that when the organic compounds that will become the electron transport layer 10, the light emitting layer 6, and the hole transport layer 7 have low solvent solubility, it is preferable to use the vacuum deposition method or the ESDUS method.
[0123] When forming the electron transport layer 10, the light-emitting layer 6, and the hole transport layer 7 using a coating method, the organic compounds that will become the electron transport layer 10, the light-emitting layer 6, and the hole transport layer 7 are dissolved in a solvent, respectively, to form organic compound solutions containing the organic compounds that will become the electron transport layer 10, the light-emitting layer 6, and the hole transport layer 7, respectively.
[0124] As the solvent used for dissolving the organic compounds to be the electron transport layer 10, the light emitting layer 6, and the hole transport layer 7, for example, aromatic hydrocarbon solvents such as xylene, toluene, cyclohexylbenzene, dihydrobenzofuran, trimethylbenzene, and tetramethylbenzene; aromatic heterocyclic compound solvents such as pyridine, pyrazine, furan, pyrrole, thiophene, and methylpyrrolidone; and aliphatic hydrocarbon solvents such as hexane, pentane, heptane, and cyclohexane are preferable, and these can be used alone or in combination.
[0125] As a method for applying an organic compound solution containing an organic compound that will become the electron transport layer 10, the light emitting layer 6, and the hole transport layer 7, various application methods can be used, such as spin coating, casting, microgravure coating, gravure coating, bar coating, roll coating, wire bar coating, dip coating, spray coating, screen printing, flexographic printing, offset printing, and inkjet printing. Among these application methods, it is preferable to use spin coating or slit coating, since it is easier to control the film thickness.
[0126] Next, the hole injection layer 8 and the anode 9 are formed in this order on the hole transport layer 7. When the hole injection layer 8 is made of an inorganic material, the hole injection layer 8 can be formed in the same manner as the oxide layer 4, for example. When the hole transport layer 9 is made of an organic material, the hole injection layer 8 can be formed in the same manner as the electron transport layer 10, the light emitting layer 6, and the hole transport layer 7, for example. The anode 9 can be formed, for example, in the same manner as the cathode 3 . By the above steps, the organic EL element 1 shown in FIG. 4 is obtained.
[0127] Next, as an example of a method for producing an organic EL element of the present invention, a method for producing an organic EL element 2 having a forward structure shown in FIG. 5 will be described. To manufacture the organic EL element 2 shown in FIG. 5, first, an anode 9 is formed on a substrate 2 . The anode 9 can be formed by a sputtering method, a vacuum deposition method, a sol-gel method, a spray pyrolysis (SPD) method, an atomic layer deposition (ALD) method, a vapor phase deposition method, a liquid phase deposition method, etc. The anode 9 may be formed by bonding a metal foil.
[0128] Next, the hole injection layer 8 is formed on the anode 9 . The hole injection layer 8 can be formed by the above-mentioned method for producing an organic thin film.
[0129] Next, on the hole injection layer 8, the hole transport layer 7, the light emitting layer 6, the electron transport layer 10, and the electron injection layer 5 are formed in this order. The methods for forming the hole transport layer 7, the light emitting layer 6, the electron transport layer 10, and the electron injection layer 5 are not particularly limited, and various conventionally known formation methods can be used as appropriate in accordance with the properties of the materials used for each of the hole transport layer 7, the light emitting layer 6, the electron transport layer 10, and the electron injection layer 5.
[0130] Specifically, methods for forming the hole transport layer 7, the light emitting layer 6, the electron transport layer 10, and the electron injection layer 5 include a coating method in which an organic compound solution containing an organic compound that will become the hole transport layer 7, the light emitting layer 6, the electron transport layer 10, and the electron injection layer 5 is applied, a vacuum deposition method, an ESDUS (Evaporative Spray Deposition from Ultra-dilute Solution) method, and the like.
[0131] When the hole transport layer 7, the light emitting layer 6, the electron transport layer 10, and the electron injection layer 5 are formed by using a coating method, the organic compounds to be the hole transport layer 7, the light emitting layer 6, the electron transport layer 10, and the electron injection layer 5 are dissolved in a solvent, respectively, to form organic compound solutions containing the organic compounds to be the hole transport layer 7, the light emitting layer 6, the electron transport layer 10, and the electron injection layer 5, respectively.
[0132] Examples of the solvent used to dissolve the organic compounds that will become the hole transport layer 7, the light emitting layer 6, the electron transport layer 10, and the electron injection layer 5 include ketone solvents such as methyl ethyl ketone (MEK), acetone, diethyl ketone, methyl isobutyl ketone (MIBK), methyl isopropyl ketone (MIPK), diisobutyl ketone, 3,5,5-trimethylcyclohexanone, diacetone alcohol, cyclopentanone, and cyclohexanone; alcohol solvents such as methanol, ethanol, isopropanol, ethylene glycol, diethylene glycol (DEG), and glycerin; Ether solvents such as diethyl ether, diisopropyl ether, 1,2-dimethoxyethane (DME), 1,4-dioxane, tetrahydrofuran (THF), tetrahydropyran (THP), anisole, diethylene glycol dimethyl ether (diglyme), diethylene glycol ethyl ether (carbitol), and other ether solvents; cellosolve solvents such as methyl cellosolve, ethyl cellosolve, and phenyl cellosolve; aliphatic hydrocarbon solvents such as hexane, pentane, heptane, and cyclohexane; toluene, xylene, benzene, cyclohexylbenzene, and other Aromatic hydrocarbon solvents such as benzene, dihydrobenzofuran, trimethylbenzene, and tetramethylbenzene; aromatic heterocyclic compound solvents such as pyridine, pyrazine, furan, pyrrole, thiophene, and methylpyrrolidone; amide solvents such as N,N-dimethylformamide (DMF) and N,N-dimethylacetamide (DMA); halogen compound solvents such as chlorobenzene, dichloromethane, chloroform, and 1,2-dichloroethane; ester solvents such as ethyl acetate, methyl acetate, and ethyl formate; sulfur compounds such as dimethyl sulfoxide (DMSO) and sulfolane. Examples of suitable organic solvents include various organic solvents such as compound solvents, nitrile solvents such as acetonitrile, propionitrile, and acrylonitrile, and organic acid solvents such as formic acid, acetic acid, trichloroacetic acid, and trifluoroacetic acid. Among these, ketone solvents such as methyl ethyl ketone (MEK), acetone, diethyl ketone, methyl isobutyl ketone (MIBK), methyl isopropyl ketone (MIPK), diisobutyl ketone, 3,5,5-trimethylcyclohexanone, diacetone alcohol, and cyclopentanone are preferred, and these can be used alone or in combination.
[0133] As a method for applying an organic compound solution containing an organic compound to become the hole transport layer 7, the light emitting layer 6, the electron transport layer 10, and the electron injection layer 5, various application methods such as spin coating, casting, microgravure coating, gravure coating, bar coating, roll coating, wire bar coating, dip coating, spray coating, screen printing, flexographic printing, offset printing, inkjet printing, etc. Among these application methods, it is preferable to use spin coating or slit coating because it is easier to control the film thickness.
[0134] Next, the cathode 3 is formed. The cathode 3 can be formed, for example, in the same manner as the anode 9. By the above steps, the organic EL element 2 shown in FIG. 5 is obtained.
[0135] "Sealing method" When the organic EL element 1 shown in FIG. 4 and the organic EL element 2 shown in FIG. 5 are sealed, they can be sealed by using a normal method used for sealing organic EL elements.
[0136] The organic EL device 1 of the embodiment shown in Fig. 4 has an electron injection layer 5 made of an organic thin film containing the first material, which is an electron-donating organic material described above, and the second material, which transports electrons, and thus the first material forms hydrogen bonds with the second material, generating negative charges and providing excellent electron injection properties. Therefore, the organic EL device 1 has a high speed of electron injection and transport from the cathode 3 to the light-emitting layer 6 and a low driving voltage. As described above, an organic EL element 1 in which an organic thin film containing a first material, which is an electron-donating organic material described above, and a second material, which transports electrons, is a laminated film, and the layer formed of the second material is a layer different from the electron injection layer formed of the first material, is also another embodiment of the organic EL element of the present invention. In the organic EL element of such an embodiment, the speed of electron injection and electron transport from the cathode 3 to the light-emitting layer 6 is fast, and the organic EL element 1 has a low driving voltage.
[0137] 5, the first material, which is an electron-donating organic material described above, forms a coordinate bond with the adjacent cathode material, generating a negative charge, thereby obtaining excellent electron injection properties. Therefore, the organic EL element 2 has a high speed of electron injection and transport from the cathode 3 to the light-emitting layer 6, and has a low driving voltage. As described above, an organic EL element 2 in which an organic thin film containing a first material, which is an electron-donating organic material described above, and a second material, which is a compound into which electrons are difficult to inject from the cathode even when an alkali metal is added, is a laminated film, and the layer formed by the second material is a layer different from the electron injection layer formed by the first material, is also another embodiment of the organic EL element of the present invention. In the organic EL element of such an embodiment, the speed of electron injection and electron transport from the cathode 3 to the light-emitting layer 6 is fast, and the organic EL element 2 has a low driving voltage.
[0138] "Other examples" The organic EL element of the present invention is not limited to the organic EL element described in the above-mentioned embodiment. Specifically, in the above-mentioned embodiment, the organic thin film functions as an electron injection layer, but the organic EL element of the present invention may have an organic thin film between the cathode and the light-emitting layer. Therefore, the organic thin film is not limited to the electron injection layer, and may be provided as a layer that functions both as the electron injection layer and the electron transport layer, or may be provided as the electron transport layer.
[0139] In the organic EL element 1 shown in FIG. 4, the inorganic oxide layer 4, the electron transport layer 10, the hole transport layer 7, and the hole injection layer 8 may be formed as necessary, and may not be provided. In addition, each of the cathode 3, the oxide layer 4, the electron injection layer 5, the electron transport layer 10, the light emitting layer 6, the hole transport layer 7, the hole injection layer 8, and the anode 9 may be formed as a single layer or may be formed as two or more layers.
[0140] In addition, the organic EL element 1 shown in Fig. 4 may have other layers between the layers shown in Fig. 4. Specifically, for the purpose of further improving the characteristics of the organic EL element, an electron blocking layer or the like may be provided as necessary.
[0141] In addition, in the above-described embodiment, an organic EL element having an inverted structure in which the cathode 3 is disposed between the substrate 2 and the light-emitting layer 6 has been described as an example, but the organic EL element may have a normal structure in which an anode is disposed between the substrate and the light-emitting layer. In the organic EL element 2 having a forward structure shown in FIG. 5, the electron transport layer 10, the hole transport layer 7, and the hole injection layer 8 may be formed as necessary, and may not be provided. In addition, each of the anode 9, the hole injection layer 8, the hole transport layer 7, the light emitting layer 6, the electron transport layer 10, the electron injection layer 5, and the cathode 3 may be formed as a single layer or may be formed as two or more layers.
[0142] In addition, the organic EL element 2 shown in Fig. 5 may have other layers between the layers shown in Fig. 5. Specifically, for the purpose of further improving the characteristics of the organic EL element, a hole blocking layer or the like may be provided as necessary.
[0143] The organic EL element of the present invention can change the emission color by appropriately selecting the materials for the light-emitting layer, etc., and can also obtain a desired emission color by using a color filter, etc. Therefore, it can be suitably used as a light-emitting portion of a display device or a lighting device.
[0144] The display device of the present invention includes the organic EL element of the present invention, which has an organic thin film between the cathode and the light-emitting layer, has excellent productivity, and has a low driving voltage, and is therefore preferable as a display device. Furthermore, the lighting device of the present invention has excellent productivity and includes the organic EL element of the present invention, which has a low driving voltage, and is therefore preferable as a lighting device.
[0145] The present invention is not limited to the above-described embodiment, and the organic thin film of the present invention can be used in devices such as organic thin film solar cells, photoelectric conversion elements, and thin film transistors. The organic thin-film solar cell or photoelectric conversion element of the present invention includes an organic thin-film. For example, when the organic thin-film is used as an electron injection layer of an organic thin-film solar cell or photoelectric conversion element, hydrogen bonds are formed between the first material and the second material of the organic thin-film, resulting in negative charges, and thus a high electron transport rate and high power generation efficiency. Therefore, the organic thin-film solar cell or photoelectric conversion element including the organic thin-film of the present invention is preferable as an organic thin-film solar cell or photoelectric conversion element. The thin film transistor of the present invention also includes an organic thin film. For example, when the channel layer of the thin film transistor is formed of an organic thin film, a channel layer with high electron mobility can be obtained. Furthermore, when the organic thin film is formed on an electrode, a reduction in contact resistance can be expected. Thus, the organic thin film of the present invention is suitable as a material for organic thin film solar cells, photoelectric conversion elements, and thin film transistors, and therefore the compound having the structure represented by the above general formula (1) constituting the organic thin film is also suitable as a material for these elements. Such materials for organic thin film solar cells, materials for photoelectric conversion elements, and materials for thin film transistors, which contain the compound having the structure represented by the above general formula (1), also constitute the present invention. EXAMPLES
[0146] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, "%" means "mol %".
[0147] Synthesis Example 1 The boron-containing compound represented by the following formula (11) was synthesized by the method described below.
[0148] [ka]
[0149] Under an argon atmosphere, ethyldiisopropylamine (39 mg, 0.30 mmol) was added to a dichloromethane solution (0.3 ml) containing 5-bromo-2-(4-bromophenyl)pyridine (94 mg, 0.30 mmol) represented by formula (10). Then, boron tribromide (1.0 M dichloromethane solution, 0.9 ml, 0.9 mmol) was added at 0°C, and the mixture was stirred at room temperature for 9 hours to react. Then, the reaction solution was cooled to 0°C, a saturated aqueous potassium carbonate solution was added, and the mixture was extracted with chloroform. Then, the organic layer was washed with saturated saline, dried over magnesium sulfate, and filtered. Then, the filtrate was concentrated with a rotary evaporator, and the resulting white solid was filtered and washed with hexane to obtain a boron-containing compound (40 mg, 0.082 mmol) represented by the above formula (11) in a yield of 28%. The boron-containing compounds obtained were identified as 1 H-NMR was used. 1 H-NMR(CDCl3):7.57-7.59(m,2H),7.80(dd,J=8.4,0.6Hz,1H),7.99(s,1H),8.27(dd,J=8.4,2.1Hz,1H),9.01(d,J=1.5Hz,1H).
[0150] Synthesis Example 2 Using the boron-containing compound represented by the above formula (11), a boron-containing compound represented by the following formula (12) was synthesized by the method shown below.
[0151] [ka]
[0152] Magnesium (561 mg, 23.1 mmol) was placed in a 50 mL two-neck flask, and the inside of the reaction vessel was filled with nitrogen. Then, cyclopentyl methyl ether (CPME) (10 mL) was added, a piece of iodine was added, and the mixture was stirred until the color disappeared. Next, a cyclopentyl methyl ether solution (9 mL) of 2,2'-dibromobiphenyl (3.0 g, 9.6 mmol) was dropped into the reaction vessel, and the mixture was stirred at room temperature for 12 hours and at 50°C for 1 hour to prepare the Grignard reagent. In another 200 mL three-neck flask, the boron-containing compound represented by the above formula (11) (3.71 g, 7.7 mmol) was placed under a nitrogen atmosphere, and toluene (77 mL) was added. While stirring at -78°C, the above Grignard reagent was added at once using a cannula. After stirring for 10 minutes, the temperature was raised to room temperature and stirred for a further 12 hours. Water was added to this reaction solution, and extraction was performed with toluene. The organic layer was washed with saturated saline, dried over magnesium sulfate, and filtered. The filtrate was then concentrated, and the residue was purified by column chromatography to obtain 3.0 g of the boron-containing compound represented by the above formula (12) (yield 82%). The boron-containing compounds obtained were identified as 1 H-NMR was used. 1 H-NMR(CDCl3):6.85(d,J=7.04Hz,2H),7.05(t,J=7.19Hz,2H),7.32(t,J=7.48Hz,2H), 7.47(s, 1H)7.49-7.57(m, 1H),7.74-7.84(m,3H),7.90-8.00(m,2H),8.07-8.20(m,1H).
[0153] Synthesis Example 3 Using the boron-containing compound represented by the above formula (12), a boron compound A represented by the following formula (14) was synthesized by the method shown below.
[0154] [ka]
[0155] In a 50 mL two-neck flask, the boron-containing compound represented by formula (12) (2.50 g, 5.26 mmol), 6-tri(n-butylstannyl)-2,2'-bipyridine represented by formula (13) (5.62 g, 12.6 mmol), Pd(PPh3)4 (610 mg, 0.53 mmol), and toluene (26 mL) were placed. The flask was then filled with nitrogen and the mixture was stirred at 120°C for 24 hours to react. The reaction solution was then cooled to room temperature and concentrated, and the residue was purified by column chromatography to obtain 2.0 g (yield 60%) of boron compound A represented by formula (14). The identification of the obtained boron compound A was as follows: 1 H-NMR was used. 1 H-NMR(CDCl3):6.6.96(d,J=6.8Hz,2H),7.04(t,J=7.2Hz,2H),7.29-7.35(m,4H),7.49(d,J=7.8Hz,1H),7.73-7.85(m,7H),8.01(d,J=0. 8Hz,1H),8.16(d,J=8.4Hz,1H),8.23(d,J=8.6Hz,1H),8.30-8.42(m,5H),8.60(d,J=8.0Hz,1H),8.66-8.67(m,2H),8.89(d,J=8.0Hz,1H).
[0156] Synthesis Example 4 The compound represented by the following formula (15) was synthesized by the method shown below.
[0157] [ka]
[0158] In a 100 mL round-bottom flask, a mixture of 4,7-dichloro-1,10-phenanthroline (3.00 g) and pyrrolidine (19.5 mL) was heated to reflux in an oil bath at 100°C for 1 hour. The mixture was returned to room temperature and concentrated under reduced pressure, water was added, and the precipitated solid was filtered out by ultrasonic treatment. The obtained solid was dried under reduced pressure and then dissolved in methanol (100 mL). Activated carbon was added to the mixture and stirred at room temperature for 1 hour, after which the insoluble matter was filtered off. The filtrate was concentrated under reduced pressure, and the obtained solid was recrystallized from methanol (9 mL). The obtained solid was washed with a small amount of methanol and dried under reduced pressure to obtain the compound represented by formula (15) (1.69 g, 44%) as a white solid.
[0159] Synthesis Example 5 <Synthesis of Monomers for Boron-Containing Polymers> A 300 mL reaction vessel was charged with the compound represented by the following formula (16) (3.96 g), 4-pyridineboronic acid (1.03 g), Pd(PPh3)4 (0.24 g), sodium carbonate (2.24 g), toluene (40 mL), distilled water (40 mL), and ethanol (20 mL). The resulting suspension was stirred for 10 minutes while bubbling with argon, then heated to 95°C in an oil bath and stirred for 18 hours at the same temperature. Water (100 mL) and toluene (100 mL) were added to the resulting yellow solution to separate it into two layers. The organic layer was washed with water and saturated saline in sequence, and then concentrated. The resulting residue was purified by column chromatography and preparative GPC to obtain a colorless solid. This was recrystallized from ethanol / hexane to obtain a compound represented by the following formula (17) (0.69 g).
[0160] [ka]
[0161] <Synthesis of boron-containing polymers> In an argon atmosphere, the compound represented by the above formula (17) (0.5 g), the compound represented by the following formula (18) (0.57 g), Pd(PPh3)4 (0.1 g), sodium carbonate (0.472 g), Aliquat336 (0.2 g), toluene (10 mL), and distilled water (10 mL) were added to a 50 mL pressure test tube. After argon bubbling for about 15 minutes, the suspension was stirred for 24 hours while heating at 100 ° C in an oil bath. Iodobenzene (0.181 g) was added to the suspension and stirred at the same temperature for 18 hours, after which phenylboronic acid (0.217 g) was added and stirred for 18 hours. The organic layer of the resulting black-brown suspension was filtered through Celite, and the filtrate was concentrated. The resulting residue was purified by column purification to obtain a light brown powder. Heptane and ethanol were added to the mixture, which was then heated, dispersed and washed. After cooling, the solid was filtered and washed with ethanol, yielding 0.61 g of boron-containing polymer (9).
[0162] [ka]
[0163] Synthesis Example 6 The compound represented by the following formula (19) was synthesized by the method shown below.
[0164] [ka]
[0165] In a 300 mL round-bottom flask, a mixture of 4,7-dichloro-1,10-phenanthroline (3.00 g) and piperidine (47 mL) was heated and stirred for 3 hours in an oil bath at 120° C. Water (250 mL) was added to the mixture, which was returned to room temperature, and the mixture was stirred for 1 hour. The precipitate was then filtered to obtain 4.47 g of the compound represented by formula (19) as a beige solid.
[0166] Synthesis Example 7 The compound represented by the following formula (20) was synthesized by the method shown below.
[0167] [ka]
[0168] In a 200 mL round-bottom flask, a mixture of 4,7-dichloro-1,10-phenanthroline (1.99 g) and morpholine (27.6 mL) was heated and stirred in an oil bath at 120°C for 3 hours. Water was added to the mixture, which was returned to room temperature, and the mixture was extracted with chloroform. The separated organic layer was dried over anhydrous sodium sulfate, and unnecessary substances were filtered off. The filtrate was concentrated under reduced pressure, and the residue was washed with ethyl acetate to obtain the compound represented by formula (20) (2.03 g, 72%) as a pale pink solid.
[0169] Examples 1 and 2 An organic EL device 1 shown in FIG. 4 was produced by the method described below and evaluated. [Process 1] As the substrate 2, a commercially available transparent glass substrate having an average thickness of 0.7 mm and having an electrode (cathode 3) patterned to a width of 3 mm and made of ITO with a thickness of 150 nm was prepared. Then, the substrate 2 having the cathode 3 was ultrasonically cleaned in acetone and isopropanol for 10 minutes each, and boiled in isopropanol for 5 minutes. Thereafter, the substrate 2 having the cathode 3 was taken out of the isopropanol, dried by nitrogen blowing, and subjected to UV ozone cleaning for 20 minutes.
[0170] [Process 2] The substrate 2 on which the cathode 3 cleaned in [Step 1] was formed was fixed to a substrate holder of a Miratron sputtering device having a zinc metal target. The chamber of the sputtering device was filled with about 1×10 -4 After reducing the pressure to 100 Pa, sputtering was performed while introducing argon and oxygen, to form a zinc oxide layer (oxide layer 4) with a thickness of about 7 nm on the cathode 3 of the substrate 2. Note that when forming the zinc oxide layer, care was taken to prevent the formation of a zinc oxide film on a portion of the ITO electrode (cathode 3) in order to allow for electrode extraction. The substrate 2 on which the oxide layer 4 had been formed was annealed at 400°C for 1 hour in air.
[0171] [Process 3] Next, an organic thin film containing a first material and a second material was formed as the electron injection layer 5 on the oxide layer 4 by the method described below. First, the boron compound A and the phenanthroline derivative (weight ratio 1:0:05) synthesized in Synthesis Examples 1 to 3 were dissolved in cyclopentanone (concentration 1 wt%) to obtain a coating composition. Next, the cathode 3 prepared in [Step 2] and the substrate 2 on which the oxide layer 4 was formed were placed on a spin coater. Then, while dropping the coating composition onto the oxide layer 4, the substrate 2 was rotated at 3000 rpm for 30 seconds to form a coating film. Thereafter, annealing was performed at 120° C. for 2 hours using a hot plate in a nitrogen atmosphere to form an electron injection layer 5. The obtained electron injection layer 5 had an average thickness of 20 nm. As the phenanthroline derivative, which is the first material, the following compound 1 was used in Example 1, and the following compound 2 was used in Example 2. Compound 1 was synthesized with reference to a known compound described in European Journal of Organic Chemistry (2017), 2017, (14), 1902-1910. Compound 2 was a commercially available product.
[0172] [ka]
[0173] [Step 4] Next, the substrate 2 on which each layer up to the electron injection layer 5 had been formed was fixed to a substrate holder of a vacuum deposition apparatus. Bis[2-(2-benzothiazolyl)phenolato]zinc(II) (Zn(BTZ)2) represented by the following formula (24), tris[1-phenylisoquinoline]iridium(III) (Ir(piq)3) represented by the following formula (23), N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4,4'-diamine (α-NPD) represented by the following formula (22), and tetrahydrofuran (TFA) ... N4,N4'-bis(dibenzo[b,d]thiophen-4-yl)-N4,N4'-diphenylbiphenyl-4,4'-diamine (DBTPB) represented by formula (21), 1,4,5,8,9,12-hexaazatriphenylene-2,3,6,7,10,11-hexacarbonitrile (HAT-CN) represented by formula (25) below, and Al were each placed in an alumina crucible and set as an evaporation source.
[0174] [ka]
[0175] Then, the inside of the chamber of the vacuum deposition device was 1×10 -5 The pressure was reduced to 100 Pa, and an electron transport layer 10, a light emitting layer 6, a hole transport layer 7, a hole injection layer 8, and an anode 9 were successively formed by a vacuum deposition method using resistance heating.
[0176] First, an electron transport layer 10 made of Zn(BTZ)2 and having a thickness of 10 nm was formed. Then, Zn(BTZ)2 was co-deposited as a host and Ir(piq)3 was co-deposited as a dopant to a thickness of 30 nm to form an emitting layer 6. At this time, the doping concentration of Ir(piq)3 was set to 6 mass% relative to the entire emitting layer 6. Next, on the substrate 2 on which the emitting layer 6 had been formed, a film of DBTPB was formed to a thickness of 10 nm and α-NPD was formed to a thickness of 30 nm to form a hole transport layer 7. Furthermore, a film of HAT-CN was formed to a thickness of 10 nm to form a hole injection layer 8. Next, on the substrate 2 on which the hole injection layer 8 had been formed, a film of anode 9 made of aluminum and having a thickness of 100 nm was formed by vacuum deposition.
[0177] The anode 9 was formed using a stainless steel deposition mask so that the deposition surface would be in the shape of a strip with a width of 3 mm, and the light-emitting area of the fabricated organic EL element was 9 mm 2 It was decided.
[0178] [Step 5] Next, the substrate 2 on which each layer up to the anode 9 was formed was placed in a glass cap (sealing container) having a concave space, and sealed by filling it with a sealant made of an ultraviolet (UV) curable resin, thereby obtaining the organic EL elements of Examples 1 and 2.
[0179] Comparative Example 1 An organic EL device of Comparative Example 1 was prepared in the same manner as in Examples 1 and 2, except that no phenanthroline derivative was used.
[0180] Voltage was applied to the thus obtained elements of Examples 1 and 2 and Comparative Example 1 using a Keithley 2400 Source Meter, and the luminance was measured using a Konica Minolta LS-100 to examine the relationship between the applied voltage and the luminance. The relationship between the applied voltage and the current density was also examined. Furthermore, the relationship between the current density and the external quantum efficiency was calculated from the obtained correlation between the luminance, voltage, and current value. These results are shown in Figures 15 to 17.
[0181] 15 to 17, the devices of Examples 1 and 2 in which the electron injection layer was doped with a phenanthroline derivative achieved high luminance at a low applied voltage and also had high external quantum efficiency, compared to the device of Comparative Example 1. In addition, when Example 1 and Example 2 are compared, Example 1, which used a phenanthroline derivative with a large electrostatic potential, achieved better characteristics than Example 2. This is believed to be due to the fact that the phenanthroline derivative acted as an n-type dopant that generates negative charges in the boron compound, resulting in improved electron injection and transport properties.
[0182] Examples 3 to 5 By the method described below, an organic thin film containing the first material and the second material was formed as the electron injection layer 5 on the oxide layer 4. The substrate 2 on which the oxide 4 had been formed was fixed to a substrate holder of a vacuum deposition device. Then, an organic thin film containing a boron compound A and a phenanthroline derivative (weight ratio 1:0:05) and having a thickness of 10 nm was formed by co-deposition. The organic EL devices of Examples 3 to 5 were produced by the same method as in Example 1 except for the above. As the phenanthroline derivative, which is the first material, the following compound 3 was used in Example 3, the following compound 4 was used in Example 4, and the above compound 2 was used in Example 5. Both compounds 3 and 4 were commercially available products.
[0183] [ka]
[0184] Comparative Example 2 An organic EL device of Comparative Example 2 was produced in the same manner as in Examples 3 to 5, except that no phenanthroline derivative was used.
[0185] Voltage was applied to the thus obtained elements of Examples 3 to 5 and Comparative Example 2 using a Keithley 2400 Source Meter, and the luminance was measured using a Konica Minolta LS-100 to examine the relationship between the applied voltage and the luminance. The relationship between the applied voltage and the current density was also examined. Furthermore, the relationship between the current density and the external quantum efficiency was calculated from the obtained correlation between the luminance, voltage, and current value. These results are shown in Figures 18 to 20.
[0186] As can be seen from Figures 18 to 20, the devices of Examples 3 to 5 in which the phenanthroline derivative was doped into the electron injection layer obtained high luminance at a low applied voltage and also had high external quantum efficiency compared to the device of Comparative Example 2. Furthermore, when comparing Examples 3 to 5, the example using the phenanthroline derivative with a large electrostatic potential obtained better characteristics. This is believed to be the result of the phenanthroline derivative acting as an n-type dopant that generates negative charges in the boron compound, resulting in improved electron injection and transport properties.
[0187] Example 6 An organic thin film containing the first material and the second material was formed as the electron injection layer 5 on the oxide layer 4 by the method described below. The substrate 2 on which the oxide 4 had been formed was fixed to a substrate holder of a vacuum deposition device. Then, an organic thin film containing the boron compound A and the compound 2 (weight ratio 1:0:05) and having a thickness of 5 nm was formed by co-deposition. Furthermore, an organic thin film containing only the boron compound and having a thickness of 5 nm was formed to form the electron injection layer 5 having a total thickness of 10 nm. The organic EL device of Example 6 was fabricated by the same method as Example 1 except for the above.
[0188] Example 7 By the method described below, an organic thin film containing the first material and the second material was formed as the electron injection layer 5 on the oxide layer 4. The substrate 2 on which the oxide 4 had been formed was fixed to a substrate holder of a vacuum deposition apparatus. An organic thin film having a thickness of 5 nm and consisting only of the boron compound A was formed, and then an organic thin film having a thickness of 5 nm containing the boron compound and the compound 2 (weight ratio 1:0:05) was formed by co-deposition to form an electron injection layer 5 having a total thickness of 10 nm. The organic EL device of Example 7 was produced by the same method as in Example 1 except for the above.
[0189] Voltage was applied to the thus obtained elements of Examples 6 and 7 using a Keithley 2400 Source Meter, and the luminance was measured using a Konica Minolta LS-100 to examine the relationship between the applied voltage and the luminance. The relationship between the applied voltage and the current density was also examined. Furthermore, the relationship between the current density and the external quantum efficiency was calculated from the obtained correlation between the luminance, voltage, and current value. These results were compared with those of Comparative Example 2. The results are shown in Figures 21 to 23. The luminance was also measured while the elements of Examples 6 and 7 were continuously driven. The results are shown in Figure 24.
[0190] As can be seen from Figures 21 to 23, when comparing Examples 6 and 7, Example 6, in which Compound 2 is doped in the electron injection layer on the layer side closer to the oxide layer 4, has slightly better characteristics. This is thought to be due to the interaction between phenanthroline and the oxide layer, as reported in Non-Patent Documents 10 and 11. On the other hand, even in Example 7, which does not contain Compound 2 near the oxide layer 4, a significant reduction in voltage is observed compared to Comparative Example 2. This is thought to be the result of the phenanthroline derivative acting as an n-type dopant that generates negative charges in the boron compound, resulting in improved electron injection and transport properties. In Examples 1 to 6, the effect of the interaction between phenanthroline and the oxide layer 4 is also thought to be included in the reduction in voltage, but as shown in Example 7, a significant reduction in voltage due to the phenanthroline derivative was observed even in a system that does not interact with the substrate. This result indicates the validity of the electron injection promotion caused by the formation of hydrogen bonds proposed in the present invention. 24, which shows the luminance decay when the elements of Examples 6 and 7 were driven continuously, confirms that Example 7, in which the substrate and the phenanthroline derivative do not interact, has a longer life than Example 6, in which the substrate and the phenanthroline derivative do interact. From this result, it can be said that Example 6, which utilizes hydrogen bonding, is more suitable for extending the life, whereas the stability of the material is impaired when the substrate and the phenanthroline derivative interact.
[0191] Example 8 By the method shown below, an organic thin film containing the first material and the second material was formed as an electron injection layer 5 on the oxide layer 4 together with other materials. First, the boron-containing polymer (9) synthesized in the above Synthesis Example 5 was dissolved in DMF (concentration: 0.1% by weight) to obtain a coating composition. Next, the substrate 2 on which the oxide 4 had been formed was placed on a spin coater. Then, while dropping the coating composition onto the oxide layer 4, the substrate 2 was rotated at 3000 rpm for 30 seconds to form a coating film of 5 nm. Thereafter, the substrate 2 was annealed at 120° C. for 2 hours in a nitrogen atmosphere using a hot plate, and fixed to the substrate holder of a vacuum deposition device. Then, an organic thin film having a thickness of 5 nm containing the boron compound A and the above compound 1 (weight ratio 1:0:05) was formed by co-evaporation to form an electron injection layer 5 having a total thickness of 10 nm. Otherwise, the organic EL device of Example 8 was produced in the same manner as in Example 1.
[0192] Voltage was applied to the element of Example 8 thus obtained using a Keithley 2400 Source Meter, and the luminance was measured using a Konica Minolta LS-100 to examine the relationship between the applied voltage and the luminance. The relationship between the applied voltage and the current density was also examined. Furthermore, the relationship between the current density and the external quantum efficiency was calculated from the obtained correlation between the luminance, voltage, and current value. These results were compared with those of Example 1. The results are shown in Figures 25 to 27. Furthermore, the luminance of the element of Example 8 was measured while it was continuously driven, and the results compared with that of the element of Example 1 are shown in Figure 28.
[0193] As can be seen from Figures 25 to 27, when comparing Examples 1 and 8, Example 1, in which Compound 1 is doped in the electron injection layer on the layer side closer to the oxide layer 4, has better characteristics. This is thought to be due to the interaction between phenanthroline and the oxide layer, as reported in Non-Patent Documents 10 and 11. On the other hand, even in Example 8, which does not contain Compound 1 in the vicinity of the oxide layer 4, a significant reduction in voltage is observed compared to Comparative Example 2. This is thought to be the result of the phenanthroline derivative acting as an n-type dopant that generates negative charges in the boron compound, resulting in improved electron injection and transport properties. As in Example 7, a significant reduction in voltage due to the phenanthroline derivative was observed even in a system that does not interact with the substrate. This result indicates the validity of the electron injection promotion caused by the formation of hydrogen bonds proposed in the present invention. Also, from FIG. 28 showing the luminance decay when the elements of Examples 1 and 8 were driven continuously, it can be confirmed that Example 8, in which the substrate and the phenanthroline derivative do not interact due to the presence of a polymer, has a longer life than Example 1, in which the substrate and the phenanthroline derivative interact. From this result, it can be said that, while the stability of the material is impaired when the substrate and the phenanthroline derivative interact, Example 8, which utilizes hydrogen bonding, is more suitable for extending the life. In this way, it is possible to extend the life of the element even if a material other than the host material of the doped layer is used between the electrode (oxide) and the doped layer.
[0194] Examples 9 to 13, Comparative Example 3 Next, in order to verify that electrons can be injected only from the phenanthroline derivative, an organic thin film consisting only of the first material was formed as the electron injection layer 5 on the oxide layer 4 by the method described below. In all of Examples 9 to 13 and Comparative Example 3, [Step 1] and [Step 2] up to the formation of the oxide layer 4 and the steps [Step 4] and [Step 5] after the formation of the electron injection layer 5 were performed in the same manner as in Example 1 to prepare organic EL devices. Example 9: Compound 3 was deposited to a thickness of 10 nm by vacuum deposition. Example 10: Compound 2 was deposited to a thickness of 10 nm by vacuum deposition. Example 11: Compound 1 was deposited to a thickness of 10 nm by vacuum deposition. Example 12: The compound represented by formula (15) was deposited to a thickness of 10 nm by vacuum deposition. Example 13: A compound represented by formula (15) was dissolved in cyclopentanone (concentration: 0.5% by weight) to obtain a coating composition. Next, the cathode 3 prepared in [Step 2] and the substrate 2 on which the oxide layer 4 was formed were placed on a spin coater. Then, the coating composition was dropped onto the oxide layer 4 while the substrate 2 was rotated at 3000 rpm for 30 seconds to form a coating film. Thereafter, an annealing treatment was performed at 120°C for 2 hours using a hot plate in a nitrogen atmosphere to form an electron injection layer 5. The average thickness of the obtained electron injection layer 5 was 10 nm. Comparative Example 3: Lithium fluoride was deposited to a thickness of 1 nm and the compound represented by formula (14) was deposited to a thickness of 10 nm by vacuum deposition.
[0195] A voltage was applied to the thus obtained elements of Examples 9 to 13 and Comparative Example 3 using a Keithley 2400 Source Meter, and the luminance was measured using a Konica Minolta LS-100 to examine the relationship between the applied voltage and the luminance. The results are shown in Figure 29. Also, Figure 30 shows microscopic images of the light-emitting surfaces of the elements of Examples 12 and 13 and Comparative Example 3 when they were stored in the atmosphere without sealing.
[0196] From the results shown in FIG. 29, in Examples 9 to 13 in which a phenanthroline derivative was used in the electron injection layer 5, a higher luminance was obtained at a lower driving voltage than in Comparative Example 3 in which lithium fluoride and an electron transport material were used in the electron injection layer 5. Therefore, it is understood that high electron injection properties can be obtained even when a phenanthroline derivative alone is used in the electron injection layer. Furthermore, a comparison of the characteristics of Examples 12 and 13 shows that a better electron injection property can be obtained when the electron injection layer is formed by coating. This is considered to be due to the fact that, as described in Non-Patent Document 12, the oxide located under the electron injection layer 5 is dissolved by the coating of the electron injection layer 5, and the coordination number with phenanthroline is increased. 30, it can be seen that the devices of Examples 12 and 13 have a slower rate of deterioration of the light-emitting surface in the presence of oxygen and moisture and have higher resistance to oxygen and moisture than the device of Comparative Example 3 using lithium fluoride. This is thought to be due to the superiority of the electron injection layer using a phenanthroline derivative that can inject electrons without using an unstable alkali metal.
[0197] Examples 14 to 16, Comparative Examples 4 to 6 As the first material, a phenanthroline derivative, a compound represented by formula (15) and a commercially available compound 2 were used, and an organic EL device 2 having a normal structure shown in FIG. 5 was produced by the method described below and evaluated. [Process 1] As the substrate 2, a commercially available transparent glass substrate having an average thickness of 0.7 mm and having an electrode (anode 9) patterned to a width of 3 mm and made of ITO with a thickness of 100 nm was prepared. Then, the substrate 2 having the anode 9 was ultrasonically cleaned in acetone and isopropanol for 10 minutes each, and boiled in isopropanol for 5 minutes. Thereafter, the substrate 2 having the anode 9 was taken out of the isopropanol, dried by nitrogen blowing, and subjected to UV ozone cleaning for 20 minutes.
[0198] [Process 2] The substrate 2 on which the anode 9 cleaned in [Step 1] was formed was set on a spin coater, and a hole injection material "Clevios HIL1.3N" manufactured by Heraeus was deposited to a thickness of 10 nm as the hole injection layer 8. Then, the substrate was heated on a hot plate heated to 180° C. for one hour.
[0199] [Process 3] Next, the substrate 2 on which the hole injection layer 8 had been formed was fixed to a substrate holder of a vacuum deposition apparatus. In addition, 2,4-diphenyl-6-bis((12-phenylindolo)[2,3-a]carbazol-11-yl)-1,3,5-triazine (DIC-TRZ) represented by the following formula (26), fac-tris(3-methyl-2-phenylpyridinato-N,C2'-)iridium(III) (Ir(mppy)3) represented by the following formula (27), and N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4,4 N,N'-diamine (α-NPD), N3,N3'''-bis(dibenzo[b,d]thiophen-4-yl)-N3,N3'''-diphenyl-[1,1':2',1'':2'',1'''-quaterphenyl]-3,3'''-diamine (4DBTP3Q) represented by the following formula (28), the compound represented by formula (15) and commercially available compound 2 as the first material, various materials as the second material shown below, and Al were each placed in an alumina crucible and set up as a deposition source.
[0200] [ka]
[0201] For the second material, the compound represented by the above formula (14) was used as an example of a boron-containing compound, the compound represented by the following formula (29) was used as an example of a pyridine-containing compound, and the compound represented by the following formula (30) (commercially available product) was used as an example of a compound having a heterocycle including a carbonyl group.
[0202] [ka]
[0203] Then, the inside of the chamber of the vacuum deposition device was 1×10 -5 The pressure was reduced to 100 Pa, and a hole transport layer 7, a light emitting layer 6, an electron transport layer 10, an electron injection layer 5, and a cathode 3 were successively formed by a vacuum deposition method using resistance heating.
[0204] Specifically, first, a hole transport layer 7 having a thickness of 30 nm and made of α-NPD of 20 nm and 4DBTP3Q of 10 nm was formed. Next, DIC-TRZ was co-evaporated as a host and Ir(mppy)3 as a dopant to a thickness of 25 nm to form the light-emitting layer 6. At this time, the doping concentration of Ir(mppy)3 was set to 3 mass % relative to the entire light-emitting layer 6. Next, an electron transport layer 10 having a thickness of 40 nm and an electron injection layer 5 having a thickness of 1 nm were formed on the substrate 2 on which the light emitting layer 6 had been formed. Next, a cathode 3 made of aluminum and having a thickness of 100 nm was formed by vacuum deposition on the substrate 2 on which the electron injection layer 5 had been formed. The cathode 3 was formed using a stainless steel deposition mask so that the deposition surface would be in the shape of a strip with a width of 3 mm, and the light-emitting area of the fabricated organic EL element was 9 mm2. 2 It was decided.
[0205] In each example, the compounds used as the second material (electron transport layer) and the first material (electron injection layer) are as follows. Example 14: The compound of formula (14) was used as the second material, and the compound of formula (15) was used as the first material. Example 15: The compound of formula (29) was used as the second material, and the compound of formula (15) was used as the first material. Example 16: The compound of formula (30) was used as the second material, and the compound of formula (15) was used as the first material.
[0206] In each of the comparative examples, the compounds used as the second material (electron transport layer) and the first material (electron injection layer) are as follows. Comparative Example 4: The compound of formula (14) was used as the second material, and lithium fluoride was used as the first material. Comparative Example 5: The compound of formula (29) was used as the second material, and lithium fluoride was used as the first material. Comparative Example 6: The compound of formula (30) was used as the second material, and lithium fluoride was used as the first material.
[0207] [Step 4] Next, the substrate 2 on which each layer up to the cathode 3 was formed was placed in a glass cap (sealing container) having a concave space, and sealed by filling it with a sealant made of an ultraviolet (UV) curable resin to obtain each organic EL element.
[0208] The luminance-voltage characteristics of the elements of Examples 14 to 16 and Comparative Examples 4 to 6 were measured in the same manner as in the other Examples and Comparative Examples, and the results are shown in Figures 31, 33, and 34. The luminance of the elements of Example 14 and Comparative Example 4 was measured while they were continuously driven, and the results are shown in Figure 32.
[0209] As an example of using a boron-containing compound as the second material, in Example 14, which is the result of using the compound of formula (14), looking at FIG. 31, it can be seen that the same luminance-voltage characteristics are obtained in Example 14, in which the phenanthroline derivative shown in formula (15) is used in the electron injection layer 8, and in Comparative Example 4, in which lithium fluoride is used in the electron injection layer 8. When the phenanthroline derivative shown in formula (15) is used in an organic EL element having a normal structure, it can be said that the same electron injection property as lithium fluoride is obtained. In addition, looking at the driving stability shown in FIG. 32, it can also be seen that the same stability as lithium fluoride is obtained. Therefore, by using the phenanthroline derivative, it is possible to realize an organic EL element that can operate at a low driving voltage without using an alkali metal and has excellent driving stability.
[0210] As an example of using a pyridine-containing compound as the second material, Example 15, which shows the results of using the compound of formula (29), is shown in FIG. 33. Here, too, Example 15, in which the phenanthroline derivative represented by structural formula (15) was used in the electron injection layer 8, and Comparative Example 5, in which lithium fluoride was used in the electron injection layer 8, have comparable luminance-voltage characteristics. Next, as an example of a compound having a heterocycle containing a carbonyl group, attention is focused on Example 16, which uses the compound of formula (30). In Fig. 34, unlike Figs. 31 and 33, Example 16 provides higher luminance at a lower applied voltage than Comparative Example 6, which uses LiF. This is a result that reflects the excellent electron injection properties of the phenanthroline derivative.
[0211] Examples 17 to 20, Comparative Example 7 Organic EL devices having a normal structure were prepared and evaluated by the following method. The devices of Examples 17, 19, and 20 and Comparative Example 7 were organic EL devices having the layered structure shown in Fig. 6, and the device of Example 18 was an organic EL device having the layered structure shown in Fig. 7. [Process 1] As the substrate 2, a commercially available transparent glass substrate having an average thickness of 0.7 mm and having an electrode (anode 9) patterned to a width of 3 mm and made of ITO with a thickness of 100 nm was prepared. Then, the substrate 2 having the anode 9 was ultrasonically cleaned in acetone and isopropanol for 10 minutes each, and boiled in isopropanol for 5 minutes. Thereafter, the substrate 2 having the anode 9 was taken out of the isopropanol, dried by nitrogen blowing, and subjected to UV ozone cleaning for 20 minutes.
[0212] [Process 2] The substrate 2 on which the anode 9 cleaned in [Step 1] was formed was set on a spin coater, and a hole injection material "Clevios HIL1.3N" manufactured by Heraeus was deposited to a thickness of 10 nm as the hole injection layer 8. Then, the substrate was heated on a hot plate heated to 180° C. for one hour.
[0213] [Process 3] Next, the substrate 2 on which the hole injection layer 8 had been formed was fixed to a substrate holder of a vacuum deposition apparatus. In addition, DIC-TRZ, Ir(mppy)3, α-NPD, 4DBTP3Q, the compound represented by formula (15) as the first material, lithium fluoride (LiF), and Al were each placed in an alumina crucible and set as a deposition source.
[0214] Then, the inside of the chamber of the vacuum deposition device was 1×10 -5 The pressure was reduced to 100 Pa, and a hole transport layer 7, a light emitting layer 6, an electron transport layer 10, an electron injection layer 5, and a cathode 3 were successively formed by a vacuum deposition method using resistance heating.
[0215] Specifically, first, a hole transport layer 7 having a thickness of 30 nm and made of α-NPD of 20 nm and 4DBTP3Q of 10 nm was formed. Next, DIC-TRZ was co-evaporated as a host and Ir(mppy)3 as a dopant to a thickness of 25 nm to form the light-emitting layer 6. At this time, the doping concentration of Ir(mppy)3 was set to 3 mass % relative to the entire light-emitting layer 6. Next, on the substrate 2 on which the light-emitting layer 6 had been formed, an electron transport layer 10 made of DIC-TRZ having a thickness of 40 nm and an electron injection layer 5 having a thickness of 1 nm were formed. In Example 17, the compound represented by formula (15) was used for the electron injection layer 5, and in Comparative Example 7, LiF, which is a general electron injection material, was used for the electron injection layer 5. In Example 18, DIC-TRZ was used for the hole transport layer 7 having a thickness of 30 nm, and the other layers were the same as those in Example 17. In Example 19, the compound represented by formula (19) was used in the electron injection layer, and in Example 20, the compound represented by formula (20) was used in the electron injection layer; the rest were the same as in Example 17.
[0216] For the elements of Examples 17 to 20 and Comparative Example 7, the luminance-voltage characteristics were measured in the same manner as in the other Examples and Comparative Example, and the results are shown in FIG.
[0217] In Examples 17, 19, and 20, in which the compound represented by the general formula (1) of the present invention was used as the electron injection layer, the device operated at a driving voltage equal to or higher than that of LiF used in Comparative Example 7, indicating that the compound represented by the general formula (1) of the present invention is effectively used as the electron injection layer. In Examples 17 and 19, electrons can be particularly efficiently injected, and it can be seen that the device can operate at a lower driving voltage than the electron injection layer using LiF. Furthermore, it can be seen that in Example 18, in which the hole transport layer is DIC-TRZ, which is the light-emitting layer host, the device operates at a driving voltage equal to that of Example 17. In this way, by using a material with excellent electron injection properties, it is possible to simplify the structure of the organic EL element and reduce the number of necessary materials.
[0218] Example 21, Comparative Example 8 In Example 18, the emitting layer was composed of two types of materials, a host and a dopant. In order to demonstrate that the simple structure shown in FIG. 7 can be realized even in an organic EL element having an emitting layer composed of a single type of material, the elements of Example 21 and Comparative Example 8 were fabricated. [Process 1] As the substrate 2, a commercially available transparent glass substrate having an average thickness of 0.7 mm and having an electrode (anode 9) patterned to a width of 3 mm and made of ITO with a thickness of 100 nm was prepared. Then, the substrate 2 having the anode 9 was ultrasonically cleaned in acetone and isopropanol for 10 minutes each, and boiled in isopropanol for 5 minutes. Thereafter, the substrate 2 having the anode 9 was taken out of the isopropanol, dried by nitrogen blowing, and subjected to UV ozone cleaning for 20 minutes.
[0219] [Process 2] Next, the substrate 2 was fixed to a substrate holder of a vacuum deposition apparatus. Further, fullerene used for the hole injection layer 8, (9,10-bis(4-(9H-carbazol-9-yl)-2,6-dimethylphenyl))-9,10-diboraanthracene (CzDBA) represented by the following formula (31), a compound represented by formula (15) as the first material, lithium quinoline, and Al were each placed in an alumina crucible and set as a deposition source. Further, molybdenum trioxide used for the hole injection layer 8 was placed in a tungsten board and set.
[0220] [ka]
[0221] Then, the inside of the chamber of the vacuum deposition device was 1×10 -5The pressure was reduced to 100 Pa, and each layer was deposited by vacuum deposition using resistance heating. Molybdenum trioxide and fullerene were deposited to a thickness of 5 nm as the hole injection layer 8, and only CzDBA was deposited to a thickness of 75 nm as the combined layer of the hole transport layer 7, the light emitting layer 6, and the electron transport layer 10. Thereafter, an electron injection layer 5 having a thickness of 1 nm and a cathode 3 were formed in succession. In Example 21, the compound represented by formula (15) was used for the electron injection layer 5, and in Comparative Example 8, lithium quinoline, a common electron injection material, was used for the electron injection layer 5.
[0222] For the elements of Example 21 and Comparative Example 8, the luminance-voltage characteristics were measured in the same manner as for the other Examples and Comparative Examples, and the results are shown in FIG.
[0223] In Comparative Example 8, the driving voltage was high because it was difficult to inject electrons from lithium quinoline to CzDBA, whereas in Example 21, electrons were efficiently injected and operation was possible at a low driving voltage. In this way, by using a material with excellent electron injection properties, it is possible to simplify the structure of the organic EL element and reduce the number of necessary materials. [Explanation of symbols]
[0224] 1: organic EL element, 2: substrate, 3: cathode, 4: oxide layer, 5: electron injection layer, 6: light emitting layer, 7: hole transport layer, 8: hole injection layer, 9: anode, 10: electron transport layer.
Claims
1. An electron injecting material for an organic electroluminescence device, comprising, as a component, a phenanthroline compound having a structure represented by the following general formula (2): 【Chemistry 1】 (In general formula (2), R 4 , R 5 m may be the same or different and represents a dialkylamino group or an alkoxy group. 4 , m 5 are the same or different and represent the number 1 or 2.)
2. An organic electroluminescence element having a light-emitting layer between a cathode and an anode, 13. An organic electroluminescence device comprising a layer comprising the electron injecting material for an organic electroluminescence device according to claim 1 between said cathode and said anode.
3. 3. The organic electroluminescence device according to claim 2, further comprising a layer containing the electron injecting material for an organic electroluminescence device according to claim 1 between the cathode and the light emitting layer.
4. 4. The organic electroluminescence device according to claim 2, further comprising an inorganic oxide layer between the cathode and the layer containing the electron injecting material for an organic electroluminescence device according to claim 1.
5. A display device comprising the organic electroluminescence element according to any one of claims 2 to 4.
6. A lighting device comprising the organic electroluminescence element according to any one of claims 2 to 4.
7. An electron injection material for an organic thin-film solar cell, comprising, as a component, a phenanthroline compound having a structure represented by the following general formula (2): 【Chemistry 2】 (In general formula (2), R 4 , R 5 m may be the same or different and represents a dialkylamino group or an alkoxy group. 4 , m 5 are the same or different and represent the number 1 or 2.)
8. An organic thin-film solar cell comprising a layer containing the electron injecting material for an organic thin-film solar cell according to claim 7.
9. 1. An electron injection material for a photoelectric conversion element, comprising a phenanthroline compound having a structure represented by the following general formula (2) as a component: 【Chemistry 3】 (In general formula (2), R 4 , R 5 m may be the same or different and represents a dialkylamino group or an alkoxy group. 4 , m 5 are the same or different and represent the number 1 or 2.)
10. A photoelectric conversion element comprising a layer containing the electron injecting material for a photoelectric conversion element according to claim 9.
11. 1. An electron injecting material for a thin film transistor, comprising a phenanthroline compound having a structure represented by the following general formula (2) as a component: 【Chemistry 4】 (In general formula (2), R 4 , R 5 m may be the same or different and represents a dialkylamino group or an alkoxy group. 4 , m 5 are the same or different and represent the number 1 or 2.)
12. A thin film transistor comprising a layer containing the electron injecting material for a thin film transistor according to claim 11.
Citation Information
Patent Citations
Organic electroluminescent element material and organic electroluminescent element
JP2017157743A
Conductive film, electrode, organic electroluminescent element, display device, lighting device, and thin-film solar cell
JP2018113149A
Organic electroluminescence element
JP2019176093A
Organic electroluminescent element
JP2019179863A
Method for manufacturing of organic light emitting display device and photoresist film using the same
KR1020140117722A